Laundry care additive particles
Inorganic shells with condensation and nanoparticle layers in perfume capsules for laundry care additives provide consistent perfume release, addressing leakage inconsistencies and enhancing user experience.
Patent Information
- Application Number
- JP2024158285
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-10-16
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Laundry care additives and dryer sheets with perfume capsules experience inconsistent perfume leakage profiles due to varying rates of perfume raw materials through organic polymer shells, leading to undesirable olfactory experiences and quality control issues.
The use of inorganic shells, composed of a condensation layer and nanoparticle layer, for perfume capsules dispersed in a water-soluble carrier, which provides consistent perfume leakage rates through microchannels in the shell.
Ensures a consistent perfume release profile, maintaining fragrance intensity and consumer satisfaction by minimizing variations in perfume delivery across different usage points.
Smart Images

Figure 2024178238000028 
Figure 2024178238000029 
Figure 2024178238000030
Abstract
Description
[Technical field]
[0001] Laundry care additive particles. The composition includes a plurality of particles, the particles including a water-soluble carrier and a capsule having a substantially inorganic shell, e.g., a silica-based shell. The present disclosure further relates to methods of making and using such compositions. The present disclosure further relates to dryer sheets including capsules having a substantially inorganic shell, e.g., a silica-based shell. [Background technology]
[0002] Laundry care particulate additives and dryer sheets are formulated with perfumed core / shell capsules.Typically, the core of such capsules contains perfume, and the shell often contains polymeric materials such as aminoplasts, polyureas, or polyacrylates.These capsules are useful for delivering benefit agents to target surfaces such as fabrics.Then, at various touch points, the capsules burst and release perfume.However, perfume capsules are known to leak, thereby reducing the efficiency of perfume delivery systems.
[0003] Furthermore, perfume capsules typically encapsulate different perfume raw materials ("perfume raw materials, PRMs"). Problematically, different PRMs can leak through the capsule walls at different rates. Over time, such as while the product is in transit or storage, the perfume properties can change as some PRMs leak more than others. This can lead to a less desirable olfactory experience than the manufacturer planned, quality control issues, and even consumer dissatisfaction if the freshness profile provided by the first dose of the product differs from that provided by the last dose. Summary of the Invention [Problem to be solved by the invention]
[0004] There is a need for laundry care particulate additives and dryer sheets that contain perfume delivery systems that have improved perfume breakthrough profiles. [Means for solving the problem]
[0005] The present disclosure relates to a composition comprising a plurality of particles, the particles comprising: about 25% by weight to about 99% by weight of a water-soluble carrier; and a plurality of capsules dispersed in the water-soluble carrier, the capsules comprising a core and a shell surrounding the core, the core comprising a fragrance raw material; The shell comprises about 90% to 100% inorganic material, optionally about 95% to 100%, optionally about 99% to 100% by weight of the shell.
[0006] The present disclosure further relates to a composition comprising a plurality of particles, the particles comprising about 25% to about 99% by weight of a water soluble carrier and a plurality of capsules dispersed in the water soluble carrier, the capsules comprising a core and a shell surrounding the core, the core comprising a perfume raw material, the shell comprising a substantially inorganic first shell component comprising a condensation layer and a nanoparticle layer, the condensation layer comprising a condensation product of precursors, the nanoparticle layer comprising inorganic nanoparticles, the condensation layer comprising a substantially inorganic first shell component disposed between the core and the nanoparticle layer, and an inorganic second shell component surrounding the first shell component, the second shell component surrounding the nanoparticle layer, The precursor comprises at least one compound selected from the group consisting of formula (I), formula (II), and mixtures thereof, wherein formula (I) is (M v O z Y n ) w and Formula (II) is (M v O z Y n R 1 p ) wand for Formula (I), Formula (II), or mixtures thereof, each M is independently selected from the group consisting of silicon, titanium, and aluminum; v is the valence of M and is 3 or 4; z is 0.5 to 1.6; and each Y is independently -OH, -OR 2 ,halogen,
[0007] [ka] -NH2, -NHR 2 , -N(R 2 )2, and
[0008] [ka] R 2 is C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C 22 aryl, or 5-12 membered heteroaryl, the heteroaryl containing 1-3 ring heteroatoms selected from the group consisting of O, N, and S; R 3 H, C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C 22 aryl, or 5-12 membered heteroaryl, the heteroaryl containing 1-3 ring heteroatoms selected from O, N, and S; w is 2-2000; for formula (I), n is 0.7-(v-1); and for formula (II), n is 0-(v-1); each R 1 are independent, C1~C 30 Alkyl, C1-C 30 Alkylene, C1-C 30 C1-C alkyl substituted with one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl, and heteroaryl; 30 Alkyl and C1-C 30Alkylene, C1-C substituted with one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl, and heteroaryl; 30 alkylene, p is a positive number up to pmax, pmax=60 / [9 * Mw(R 1 )+8], and Mw(R 1 ) is R 1 is the molecular weight of the group.
[0009] The present disclosure further relates to a dryer sheet comprising a nonwoven fibrous layer and a solid fabric softener composition disposed on or within the nonwoven fibrous layer, the solid fabric softener composition comprising a plurality of capsules dispersed in the solid fabric softener composition, the capsules comprising a core and a shell surrounding the core, the core comprising a perfume raw material, the shell comprising about 90%-100%, optionally about 95%-100%, optionally about 99%-100% inorganic material by weight of the shell. [Brief description of the drawings]
[0010] [Figure 1] This is a particle production device. [Diagram 2] FIG. 1 is a schematic diagram of a method for making a capsule having a first shell component prepared with a hydrophobic core. [Diagram 3] FIG. 1 is a schematic diagram of a capsule having a first shell component and a second shell component. [Figure 4] 1 is a scanning electron microscope image of the capsule. [Diagram 5] FIG. 1 illustrates a population of capsules according to the present disclosure. [Figure 6] 1 is a box plot of the WFHS / DFHS ratio measured as described in Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present disclosure relates to laundry care additive particles comprising a water-soluble carrier and capsules containing multiple perfumes dispersed in the carrier. The capsules, when dispersed in the carrier, have consistent permeability to various perfume ingredients, which provides a consistent scent experience to the user over the period of use of the laundry care additive package and at various contact points where the user handles or wears laundry treated with such laundry care additive. The present disclosure further relates to dryer sheets comprising the capsules.
[0012] Laundry care additive particles can be useful for providing benefits to laundry throughout the wash. That is, the particles can be used by the user by dispensing the particles into the washing machine before starting the washing machine cycle, especially the wash subcycle. Through the wash compositions, such as those described herein, are different from through the rinse compositions. Through the rinse compositions are designed to be dispensed during the rinse subcycle of the washing machine. In modern washing machines, the rinse subcycle is automatically initiated after the wash subcycle is completed without further input from the consumer. Compositions dispensed during the rinse subcycle are generally dispensed into a separate dosing chamber that is part of the washing machine, such as a dispensing drawer, or from an agitator in the tub, which dispenses the through the rinse composition during the rinse subcycle.
[0013] It is believed that the type of capsules disclosed herein, when used in a water-soluble carrier, provide surprisingly good control of leakage of perfume raw materials in the compositions of the present disclosure, resulting in relatively low and consistent perfume leakage. Without being bound by theory, it is believed that leakage of perfume raw materials is caused by a fundamentally different mechanism for shells containing highly crosslinked inorganic materials compared to shells containing organic polymeric materials. Specifically, the diffusion of small molecules such as perfume raw materials ("PRMs") across homogeneous organic polymer shells is similar to the diffusion mechanism across homogeneous polymeric membranes. In this case, the permeability of the polymeric membrane to a given solute depends on both the free volume of the polymer (affected by crystallinity and crosslinking density) and the relative solubility of the solute in the polymer. Different PRMs have different ranges of relevant physical and chemical properties (e.g., molecular weight and polarity), so the diffusion rate for a given set of PRMs will not be uniform if the physical and chemical properties are also not uniform.
[0014] On the other hand, it is believed that the diffusion of small molecules across a highly crosslinked inorganic shell occurs mainly through the microchannels formed by the permeating network of micropores present in the shell. Such highly crosslinked inorganic shells can be obtained by using a second shell component in combination with a first shell component as disclosed in the present disclosure. In this case, it is believed that the permeability of the inorganic shell depends mainly on the number, density, and size of the microchannels that effectively connect the core phase and the continuous phase, which can result in relatively uniform or consistent PRM leakage rates relative to each other and relatively low.
[0015] It is further believed that because the various PRMs leak from the disclosed capsules in the disclosed compositions at a relatively consistent rate, the intended properties of the fragrance are maintained, resulting in a more satisfying and consistent olfactory performance.
[0016] The terms "substantially free of" or "substantially free from" may be used herein. This means that the indicated material is in a minimal amount and has not been intentionally added to the composition to form part of the composition, or, optionally, is not present at analytically detectable concentrations. It means that it includes compositions in which the indicated material is present only as an impurity in one of the other intentionally included materials. The indicated material may be present, if at all, at a concentration of less than 1% by weight of the composition, or less than 0.1% by weight, or less than 0.01% by weight, or even 0% by weight.
[0017] Unless otherwise noted, all component or composition levels refer to the active portion of that component or composition and are exclusive of impurities, e.g., residual solvents or by-products, which may be present in commercial sources of such component or composition.
[0018] All temperatures herein are in degrees Celsius (° C.) unless otherwise indicated. All measurements herein are made at 20° C. and atmospheric pressure unless otherwise stated.
[0019] As described herein, all percentages are by weight of the total composition unless otherwise specified. All ratios are by weight unless otherwise specified.
[0020] It should be understood that every maximum numerical limitation given throughout this specification includes every lower numerical limitation, as if such lower numerical limitation were expressly written herein. Every minimum numerical limitation given throughout this specification is intended to include every higher numerical limitation, as if such higher numerical limitations were expressly written herein. Every numerical range given throughout this specification is intended to include every narrower numerical range that falls within such broader numerical range, as if such narrower numerical ranges were all expressly written herein.
[0021] Water-soluble carrier The particles may include a water-soluble carrier that acts to carry the capsules into the wash liquor such that, upon dissolution of the water-soluble carrier, the capsules are dispersed in the wash liquor and adhere to the laundry.
[0022] The water-soluble carrier can be a material that is soluble in the wash solution for a short period of time, for example, less than about 10 minutes.
[0023] Water soluble means that the material, carrier substance, or particle is soluble or dispersible in water and optionally has at least 50%, optionally at least 75%, or even at least 95% water solubility as measured by the method hereafter presented using a glass filter with a maximum pore size of 20 micrometers: 50 grams ± 0.1 grams of carrier are added to a pre-weighed 400 mL beaker and 245 mL ± 1 mL of distilled water are added. This is vigorously stirred for 30 minutes with a magnetic stirrer set at 600 rpm. The mixture is then filtered through a sintered glass filter with a pore size (maximum 20 micrometers) as defined above. The process is carried out at a temperature of 23 ° C ± 1.0 ° C and a relative humidity of 50% ± 2%. The water is dried from the collected filtrate by any conventional method and the weight of the remaining material is determined (this is the dissolved or dispersed fraction). The solubility or dispersion percentage can then be calculated.
[0024] The water-soluble carrier may be selected from the group consisting of water-soluble inorganic alkali metal salts, water-soluble alkaline earth metal salts, water-soluble organic alkali metal salts, water-soluble organic alkaline earth metal salts, water-soluble carbohydrates, water-soluble silicates, water-soluble urea, and any combination thereof.
[0025] The alkali metal salt may be selected from the group consisting of, for example, lithium salts, sodium salts, and potassium salts, and any combination thereof. Useful alkali metal salts may be selected from the group consisting of, for example, alkali metal fluorides, alkali metal chlorides, alkali metal bromides, alkali metal iodides, alkali metal sulfates, alkali metal bisulfates, alkali metal phosphates, alkali metal monohydrogen phosphates, alkali metal dihydrogen phosphates, alkali metal carbonates, alkali metal monohydrogen carbonates, alkali metal acetates, alkali metal citrates, alkali metal lactates, alkali metal pyruvates, alkali metal silicates, alkali metal ascorbates, and combinations thereof.
[0026] The alkali metal salt may be selected from the group consisting of sodium fluoride, sodium chloride, sodium bromide, sodium iodide, sodium sulfate, sodium bisulfate, sodium phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium citrate, sodium lactate, sodium tartrate, sodium silicate, sodium ascorbate, potassium fluoride, potassium chloride, potassium bromide, potassium iodide, potassium sulfate, potassium bisulfate, potassium phosphate, potassium monohydrogen phosphate, potassium dihydrogen phosphate, potassium carbonate, potassium monohydrogen carbonate, potassium acetate, potassium citrate, potassium lactate, potassium tartrate, potassium silicate, potassium, ascorbate, and combinations thereof.
[0027] The alkaline earth metal salt may be selected from the group consisting of magnesium salts, calcium salts, and the like, and combinations thereof. The alkaline earth metal salt may be selected from the group consisting of alkali metal fluorides, alkali metal chlorides, alkali metal bromides, alkali metal iodides, alkali metal sulfates, alkali metal bisulfates, alkali metal phosphates, alkali metal monohydrogen phosphates, alkali metal dihydrogen phosphates, alkali metal carbonates, alkali metal monohydrogen carbonates, alkali metal acetates, alkali metal citrates, alkali metal lactates, alkali metal pyruvates, alkali metal silicates, alkali metal ascorbates, and combinations thereof. The alkaline earth metal salt may be selected from the group consisting of magnesium fluoride, magnesium chloride, magnesium bromide, magnesium iodide, magnesium sulfate, magnesium phosphate, magnesium monohydrogen phosphate, magnesium dihydrogen phosphate, magnesium carbonate, magnesium monohydrogen carbonate, magnesium acetate, magnesium citrate, magnesium lactate, magnesium tartrate, magnesium silicate, magnesium ascorbate, calcium fluoride, calcium chloride, calcium bromide, calcium iodide, calcium sulfate, calcium phosphate, calcium monohydrogen phosphate, calcium dihydrogen phosphate, calcium carbonate, calcium monohydrogen carbonate, calcium acetate, calcium citrate, calcium lactate, calcium tartrate, calcium silicate, calcium ascorbate, and combinations thereof.
[0028] Inorganic salts, such as inorganic alkali metal salts and inorganic alkaline earth metal salts, do not contain carbon. Organic salts, such as organic alkali metal salts and organic alkaline earth metal salts, do contain carbon. The organic salt may be an alkali metal salt or an alkaline earth metal salt of sorbic acid (i.e., a sorbate salt). The sorbate salt may be selected from the group consisting of sodium sorbate, potassium sorbate, magnesium sorbate, calcium sorbate, and combinations thereof.
[0029] The water-soluble carrier may be or may include a material selected from the group consisting of water-soluble inorganic alkali metal salts, water-soluble organic alkali metal salts, water-soluble inorganic alkaline earth metal salts, water-soluble organic alkaline earth metal salts, water-soluble carbohydrates, water-soluble silicates, water-soluble urea, and combinations thereof.The water-soluble carrier may be selected from the group consisting of sodium chloride, potassium chloride, calcium chloride, magnesium chloride, sodium sulfate, potassium sulfate, magnesium sulfate, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, sodium acetate, potassium acetate, sodium citrate, potassium citrate, sodium tartrate, potassium tartrate, potassium sodium tartrate, calcium lactate, water glass, sodium silicate, potassium silicate, dextrose, fructose, galactose, isoglucose, glucose, sucrose, raffinose, isomalt, xylitol, crystal sugar, granulated sugar, and combinations thereof.In one embodiment, the water-soluble carrier may be sodium chloride.In one embodiment, the water-soluble carrier may be table salt.
[0030] The water soluble carrier may be or include a material selected from the group consisting of sodium bicarbonate, sodium sulfate, sodium carbonate, sodium formate, calcium formate, sodium chloride, sucrose, maltodextrin, corn syrup solids, corn starch, wheat starch, rice starch, potato starch, tapioca starch, clays, silicates, carboxymethyl cellulose citrate, fatty acids, fatty alcohols, glyceryl diesters of hydrogenated tallow, glycerol, and combinations thereof.
[0031] The water-soluble carrier may be selected from the group consisting of water-soluble organic alkali metal salts, water-soluble inorganic alkaline earth metal salts, water-soluble organic alkaline earth metal salts, water-soluble carbohydrates, water-soluble silicates, water-soluble urea, starches, clays, water-insoluble silicates, carboxymethylcellulose citrate, fatty acids, fatty alcohols, glyceryl diesters of hydrogenated tallow, glycerol, polyethylene glycol, and combinations thereof.
[0032] The water soluble carrier may be selected from the group consisting of disaccharides, polysaccharides, silicates, zeolites, carbonates, sulfates, citrates, and combinations thereof.
[0033] The water-soluble carrier may be selected from the group consisting of polyethylene glycol, sodium acetate, sodium bicarbonate, sodium chloride, sodium silicate, polypropylene glycol polyoxoalkylenes, polyethylene glycol fatty acid esters, polyethylene glycol ethers, sodium sulfate, starch, and mixtures thereof.
[0034] The water-soluble carrier may be a water-soluble polymer, which may be selected from the group consisting of C8-C22 alkyl polyalkoxylates containing more than about 40 alkoxylate units, ethoxylated nonionic surfactants having an ethoxylation degree of more than about 30, polyalkylene glycols having a weight average molecular weight of about 2000 to about 15000, and combinations thereof.
[0035] The water-soluble carrier can be a water-soluble polymer. The water-soluble polymer is represented by the formula (I), (II), (III) or (IV), R 1 O-(EO)x-(PO)yR 2 (I), R 1 O--(PO)x-(EO)yR 2 (II), R 1 O-(EO)o-(PO)p-(EO)qR 2 (III), R 1 O--(PO)o-(EO)p-(PO)qR 2 (IV), or a combination thereof, in which EO is a -CH2CH2O- group, PO is a -CH(CH3)CH2O- group; R 1 and R 2 are independently H or a C1-C22 alkyl group; x, y, o, p, and q are independently 1 to 100; with the proviso that the sum of x and y is greater than 35 and the sum of o, p, and q is greater than 35; and the block copolymer has a molecular weight in the range of about 3000 g / mol to about 15,000 g / mol.
[0036] The water soluble polymer can be a block copolymer or multiple block copolymers, such as block copolymers based on ethylene oxide and propylene oxide selected from the group consisting of PLURONIC-F38, PLURONIC-F68, PLURONIC-F77, PLURONIC-F87, PLURONIC-F88, and combinations thereof. PLURONIC materials are available from BASF.
[0037] The water-soluble polymer may be selected from the group consisting of polyvinyl alcohol (PVA), modified PVA; polyvinylpyrrolidone; PVA copolymers such as PVA / polyvinylpyrrolidone and PVA / polyvinylamine; partially hydrolyzed polyvinyl acetate; polyalkylene oxides such as polyethylene oxide; polyethylene glycol; acrylamide; acrylic acid; alkylcellulosic materials such as cellulose, methylcellulose, ethylcellulose, and propylcellulose; cellulose ethers; cellulose esters; cellulose amides; polyvinyl acetate; polycarboxylic acids and salts; polyamino acids or peptides; polyamides; polyacrylamides; maleic acid / acrylic acid copolymers; polysaccharides including starch, modified starch; gelatin; alginates; other hemicellulosic polysaccharides including xyloglucan, xylan, glucuronoxylan, arabinoxylan, mannan, glucomannan, and galactoglucomannan; and natural gums such as pectin, xanthan, and carrageenan, locust bean, arabic, and tragacanth; and combinations thereof. In one embodiment, the polymer comprises polyacrylates, particularly sulfonated polyacrylates and water-soluble acrylate copolymers; and alkyl hydroxycellulose-based materials, such as methylcellulose, sodium carboxymethylcellulose, modified carboxymethylcellulose, dextrin, ethylcellulose, propylcellulose, hydroxyethylcellulose, hydroxypropylmethylcellulose, maltodextrin, polymethacrylates. In yet another embodiment, the water-soluble polymer may be selected from the group consisting of PVA; PVA copolymers; hydroxypropyl methyl cellulose (HPMC); and mixtures thereof.
[0038] Water soluble polymers include polyvinyl alcohol, modified polyvinyl alcohol, polyvinylpyrrolidone, polyvinyl alcohol / polyvinylpyrrolidone, polyvinyl alcohol / polyvinylamine, partially hydrolyzed polyvinyl acetate, polyalkylene oxide, polyethylene glycol, acrylamide, acrylic acid, cellulose, alkylcellulose-based materials, methylcellulose, ethylcellulose, propylcellulose, cellulose ethers, cellulose esters, cellulose amides, polyvinyl acetate, polycarboxylic acids and salts, polyamino acids or peptides, polyamides, polyacrylamides, maleic acid / acrylic acid copolymers, polysaccharides, starches, modified starches, gelatin, alginates, xyloglucans, hemicellulosic polysaccharides, The polysaccharide may be selected from the group consisting of xylan, glucuronoxylan, arabinoxylan, mannan, glucomannan, galactoglucomannan, natural gums, pectin, xanthan, carrageenan, locust bean, arabic, tragacanth, polyacrylates, sulfonated polyacrylates, water soluble acrylate copolymers, alkylhydroxycellulose-based materials, methylcellulose, sodium carboxymethylcellulose, modified carboxy-methylcellulose, dextrin, ethylcellulose, propylcellulose, hydroxyethylcellulose, hydroxypropylmethylcellulose, maltodextrin, polymethacrylates, polyvinyl alcohol polymers, hydroxypropylmethylcellulose, and mixtures thereof.
[0039] The water-soluble polymer may be an organic material. Organic water-soluble polymers may offer the advantage of being readily soluble in water.
[0040] The water soluble polymer may be selected from the group consisting of polyethylene glycol, polypropylene glycol polyoxoalkylene, polyethylene glycol fatty acid esters, polyethylene glycol ethers, starch, and mixtures thereof.
[0041] The water-soluble polymer may be polyethylene glycol (PEG). PEG may be a convenient material to use in making the particles because it may be water-soluble enough to dissolve during the wash cycle when the particles have a mass in the range disclosed herein. Furthermore, PEG may be easily processed as a melt. The onset of the melting temperature of PEG may vary as a function of the molecular weight of the PEG. The particles may include about 25% to about 94% by weight of PEG having a weight average molecular weight of about 2000 to about 15000. PEG is relatively low cost, can be formed into many different shapes and sizes, minimizes diffusion of unencapsulated fragrance, and is well soluble in water. PEG is provided in a variety of weight average molecular weights. Suitable weight average molecular weight ranges for PEG include about 2,000 to about 13,000, alternatively about 4,000 to about 13,000, alternatively about 4,000 to about 12,000, alternatively about 4,000 to about 11,000, alternatively about 5,000 to about 11,000, alternatively about 6,000 to about 10,000, alternatively about 7,000 to about 9,000, or combinations thereof. PEG is available, for example, from BASF as PLURIOL E8000, or other PLURIOL products. The water-soluble polymer may be a mixture of two or more polyethylene glycol compositions, one having a first weight average molecular weight (e.g., 9000) and another having a second weight average molecular weight (e.g., 4000), the second weight average molecular weight being different from the first weight average molecular weight.
[0042] The particles can comprise from about 25% to about 99% by weight of the water-soluble carrier. The particles can comprise from about 35% to about 95% by weight of the particle, optionally from about 50% to about 80% by weight, any combination thereof, and any total percentage or range of total percentages within any of the aforementioned ranges.
[0043] The plurality of particles can include individual particles comprising about 25% to about 99% by weight of the particle of a water-soluble carrier and about 0.1% to about 20% by weight of the particle of a particle capsule, the capsule being dispersed in a matrix of a water-soluble polymer.
[0044] The particles may comprise from about 25% to about 99% PEG by weight of the individual particle. Optionally, the individual particles can comprise from about 25% to about 95% PEG by weight of the particle, optionally from about 35% to about 95% PEG by weight, optionally from about 50% to about 80% PEG by weight, optionally combinations thereof, and any total percentage or range of total percentages within any of the foregoing ranges.
[0045] The water soluble polymer can include a material selected from the group consisting of: x -(CH(CH3)CH2O) y -(C2H4O) z -OH, where x is from about 50 to about 300, y is from about 20 to about 100, and z is from about 10 to about 200; a polyalkylene polymer of the formula (CHO) q -C(O)O-(CH2) r -CH3 (wherein q is about 20 to about 200 and r is about 10 to about 30); polyethylene glycol fatty acid ester of the formula HO-(C2H4O) s -CH2) t )-CH3, where s is from about 30 to about 250 and t is from about 10 to about 30; and mixtures thereof. x -(CH(CH3)CH2O) y -(C2H4O) z The polyalkylene polymer of -OH, where x is about 50 to about 300, y is about 20 to about 100, and z is about 10 to about 200, can be a block copolymer or a random copolymer.
[0046] The water soluble polymer may include: polyethylene glycol; x -(CH(CH3)CH2O) y -(C2H4O) z -OH, where x is from about 50 to about 300, y is from about 20 to about 100, and z is from about 10 to about 200; q-C(O)O-(CH2) r -CH3, where q is from about 20 to about 200 and r is from about 10 to about 30; and polyethylene glycol fatty acid esters of the formula HO-(C2H4O) s -(CH2) t )-CH3, wherein s is from about 30 to about 250, and t is from about 10 to about 30.
[0047] The water soluble polymer is from about 20% to about 95% by weight of the plurality of particles or individual particles, and has the formula H-(CHO) x -(CH(CH3)CH2O) y -(C2H4O) z The polyalkylene polymer may include a polyalkylene polymer of the formula: -OH, where x is about 50 to about 300, y is about 20 to about 100, and z is about 10 to about 200.
[0048] The water soluble polymer may be from about 1% to about 20% by weight of the plurality of particles or individual particles, of a compound of the formula (C2H4O): q -C(O)O-(CH2) r It may include a polyethylene glycol fatty acid ester of -CH3 (wherein q is about 20 to about 200, and r is about 10 to about 30).
[0049] The water-soluble polymer may be from about 1% to about 10% by weight of the plurality of particles or of each individual particle, and may be a polymer having the formula HO-(CHO) s -CH2) t )-CH3, where s is from about 30 to about 250 and t is from about 10 to about 30.
[0050] The water-soluble carrier may comprise a plasticizer polyol (0% to 3% by weight of the particles), optionally a plasticizer polymer that is liquid at 20° C. and 1 atmosphere, water (1% to 20% by weight of the particles, or 1% to 12% by weight, or 6% to 8% by weight of the particles), and a sugar alcohol polyol selected from the group consisting of erythritol, xylitol, mannitol, isomalt, maltitol, lactitol, trehalose, lactose, tagatose, sucralose, and mixtures thereof (45% to 80% by weight of the particles, or 50% to 70% by weight, or 50% to 60% by weight of the particles), and the particles may comprise (a) 15 to 20% by weight of the particles, The modified starch further includes (a) a modified starch having a dextrose equivalent of 20, wherein the sugar alcohol polyol and the modified starch are present in a weight ratio of the sugar alcohol polyol to the modified starch of 2:1 to 16:1, or 2:1 to 10:1, or 2:1 to 3:1, or (b) a modified starch having a dextrose equivalent of 4 to less than 15, wherein the sugar alcohol polyol and the modified starch are present in a weight ratio of the sugar alcohol polyol to the modified starch of 1.5:1 to 16:1, or 1.5:1 to 10:1, or 1.5:1 to 4. The modified starch may have a dextrose equivalent of 15 to 20, wherein the sugar alcohol polyol and the modified starch are present in a ratio of 2:1 to 16:1, or 2:1 to 10:1, or 2:1 to 3:1. The modified starch has a dextrose equivalent of 4 to less than 15, and the sugar alcohol polyol and the modified starch may be present in a weight ratio of the sugar alcohol polyol to the modified starch of 1.5:1 to 16:1, or 1.5:1 to 10:1, or 1.5:1 to 4:1. The modified starch may have a dextrose equivalent of 4 to 12. The modified starch may be maltodextrin. The sugar alcohol polyol may be mannitol. The plasticizer polyol may be selected from the group consisting of glycerin, dipropylene glycol, propylene glycol, and mixtures thereof.
[0051] The particles can comprise from about 25% to about 99% by weight of the water-soluble carrier. Optionally, the particles can comprise from about 35% to about 85%, or even from about 50% to about 80% by weight of the particle of the water-soluble carrier.
[0052] capsule The compositions of the present disclosure further comprise a plurality of capsules. As described in more detail below, the capsules may comprise a core surrounded by a substantially inorganic shell.
[0053] The capsules may be present in the particles of the composition in an amount of about 0.1% to about 20%, or about 0.2% to about 10%, or about 0.2% to about 5%, or about 0.2% to about 3% by weight of the composition. The composition may include a sufficient amount of capsules to provide the composition with about 0.1% to about 20%, or about 0.2% to about 10%, or about 0.2% to about 5% of the perfume raw material by weight of the composition. As discussed herein, the amount or weight percent of capsules refers to the combined shell material and core material.
[0054] The capsules can have an average shell thickness of from 10 nm to 10,000 nm, optionally from 170 nm to 1000 nm, optionally from 300 nm to 500 nm.
[0055] The capsules can have an average volume weighted capsule diameter of 0.1 micrometers to 300 micrometers, optionally 10 micrometers to 200 micrometers, optionally 10 micrometers to 50 micrometers. Advantageously, it has been found that embodiments herein can provide large capsules (e.g., average diameters of 10 mm or more) without sacrificing the overall stability of the capsule and / or while maintaining good breaking strength.
[0056] Surprisingly, it has been found that in addition to inorganic shell, volume core-to-shell ratio can also play an important role in ensuring capsule physical integrity. Shells that are too thin relative to the overall size of capsule (core:shell ratio>98:2) tend to be adversely affected by lack of self-integrity. Meanwhile, shells that are too thick relative to capsule diameter (core:shell ratio<80:20) tend to have higher shell permeability in surfactant-rich matrices. While it may be intuitive to assume that thick shells will result in lower shell permeability (because this parameter affects the average diffusion path of active substance across the shell), it has been surprisingly found that capsules of the present invention with shells that have a thickness above a threshold value have higher shell permeability. It is believed that this upper threshold value depends in part on capsule diameter.
[0057] The capsules can have a volume core to shell ratio of from 50:50 to 99:1, optionally from 60:40 to 99:1, optionally from 70:30 to 98:2, optionally from 80:20 to 96:4.
[0058] It may be desirable to have a particular combination of these capsule properties. For example, the capsules may have a volumetric core-to-shell ratio of about 99:1 to about 50:50, an average volume-weighted capsule diameter of about 0.1 mm to about 200 mm, and an average shell thickness of about 10 nm to about 10,000 nm. The capsules may have a volumetric core-to-shell ratio of about 99:1 to about 50:50, an average volume-weighted capsule diameter of about 10 mm to about 200 mm, and an average shell thickness of about 170 nm to about 10,000 nm. The capsules may have a volumetric core-to-shell ratio of about 98:2 to about 70:30, an average volume-weighted capsule diameter of about 10 mm to about 100 mm, and an average shell thickness of about 300 nm to about 1000 nm.
[0059] The methods of the present disclosure can produce capsules with a low coefficient of variation in capsule diameter. Controlling the distribution of capsule sizes can improve the breaking strength of the population and allow the population to have a more uniform breaking strength. The coefficient of variation in capsule diameter of a population of capsules can be 40% or less, optionally 30% or less, and optionally 20% or less.
[0060] For a capsule containing a core material to be functional and cost-effective in consumer product applications such as laundry care particulate additives, the capsule should i) be resistant to diffusion of the core during the shelf life of the liquid product (e.g., low leakage or permeability), ii) be capable of depositing on the targeted surface during application (e.g., during a washing machine cycle), and iii) be capable of releasing the core material by mechanically rupturing the shell at the correct time and place to provide the intended benefit to the end consumer.
[0061] The capsules described herein can have an average breaking strength of 0.1 MPa to 10 MPa, optionally 0.25 MPa to 5 MPa, optionally 0.25 MPa to 3 MPa. Fully inorganic capsules traditionally have poor breaking strength, but the capsules described herein can have a breaking strength of greater than 0.25 MPa, improving stability and allowing for triggered release of the beneficial agent upon exposure to a specified amount of burst stress.
[0062] In certain embodiments, the capsules have an average volume-weighted diameter of 1-200 micrometers, optionally 1-10 micrometers, optionally 2-8 micrometers. In other embodiments, the shell thickness is 1-10000 nm, 1-1000 nm, 10-200 nm. In further embodiments, the capsules have an average volume-weighted diameter of 1-10 micrometers and a shell thickness of 1-200 nm. Capsules having an average volume-weighted diameter of 1-10 micrometers and a shell thickness of 1-200 nm have been found to have higher fracture strength.
[0063] Without wishing to be bound by theory, it is believed that a higher breaking strength provides better survivability during the washing process, which may cause premature rupture of mechanically weak capsules due to mechanical constraints in the washing machine.
[0064] Capsules with an average volume weighted diameter of 1-10 micrometers and a shell thickness of 10-200 nm provide resistance to mechanical constraints when made with a particular selection of silica precursors used. In some embodiments, the precursors have a molecular weight of 2-5 kDa, optionally 2.5-4 kDa. In addition, the concentration of the precursor must be carefully selected, being 20-60% by weight, preferably 40-60% by weight, of the oil phase used during encapsulation.
[0065] Without being bound by theory, it is believed that higher molecular weight precursors have a much slower migration time from the oil phase to the water phase. It is believed that the slower migration time results from a combination of three phenomena: diffusion, partitioning, and reaction kinetics. This phenomenon may be important in the context of small capsules due to the fact that the total surface area between the oil and water in the system increases as the capsule diameter decreases. Higher surface area leads to higher migration of precursors from the oil phase to the water phase, thereby reducing the yield of polymerization at the interface. Thus, higher molecular weight precursors can mitigate the effects caused by increased surface area and obtain capsules according to the present invention.
[0066] i.Core The capsule comprises a core. The core may be oil-based or the core may be aqueous. Optionally, the core is oil-based. The core may be liquid at the temperature at which it is used in the formulated product. The core may be liquid at or near room temperature.
[0067] The core comprises a flavoring agent. The core may comprise about 1% to 100% by weight of flavoring agent based on the total weight of the core. Optionally, the core may comprise 50% to 100% by weight of flavoring agent based on the total weight of the core, optionally about 80% to 100% by weight of flavoring agent based on the total weight of the core. Typically, a higher level of flavoring agent is preferred for improved delivery efficiency.
[0068] A perfume may comprise one or more, optionally two or more, perfume raw materials. The term "perfume raw material" (or "perfume raw material, PRM"), as used herein, refers to a compound having a molecular weight of at least about 100 g / mole and useful for imparting odor, fragrance, essence, or scent, alone or together with other PRMs. Typical PRMs include, among others, alcohols, ketones, aldehydes, esters, ethers, nitrites, and alkenes, such as terpenes. Lists of common PRMs can be found in various reference sources, such as, for example, "Perfume and Flavor Chemicals" Vol. I and Vol. II; Steffen Arctander Allured Pub.Co. (1994) and "Perfumes: Art, Science and Technology", Miller, PM and Lamparsky, D., Blackie Academic and Professional (1994).
[0069] PRMs may be characterized by their boiling point (BP) measured at normal pressure (760 mmHg) and octanol / water partition coefficient (P), which may be described in terms of logP determined according to the test methods in the Test Methods section. Based on these characteristics, PRMs may be classified as Quadrant I, Quadrant II, Quadrant III, or Quadrant IV PRMs, as described in more detail below. A perfume having various PRMs from different quadrants may be desirable, for example, to provide a fragrance benefit at different touch points during normal use.
[0070] PRMs with a boiling point BP below about 250° C. and a logP below about 3 are known as quadrant IPRMs. Quadrant IPRMs are optionally limited to less than 30% of the perfume composition. PRMs with a BP above about 250° C. and a logP above about 3 are known as quadrant IVPRMs, PRMs with a BP above about 250° C. and a logP below about 3 are known as quadrant IIPRMs, and PRMs with a BP below about 250° C. and a logP above about 3 are known as quadrant IIIPRMs. Suitable quadrants I, II, III and IVPRMs are disclosed in U.S. Pat. No. 6,869,923 (B1).
[0071] A perfume may comprise a mixture of at least 3, or even at least 5, or at least 7 PRMs. A perfume may comprise at least 10 or at least 15 PRMs. A mixture of PRMs may provide a more complex and desirable fragrance, and / or better perfume performance or longevity, for example at various touch points. However, it may be desirable to limit the number of PRMs in a perfume to reduce or limit formulation complexity and / or cost.
[0072] The perfume may include at least one perfume raw material of natural origin. Such ingredients may be desirable for sustainability / environmental reasons. Naturally derived PRMs may include natural extracts or essences that may contain mixtures of PRMs. Such natural extracts or essences may include orange oil, lemon oil, rose extract, lavender, musk, patchouli, balsam essence, sandalwood oil, pine oil, cedar, etc.PRM is made up of: Almond Oil, Ambrette, Angelica Seed Oil, Almoise Oil, Basil Oil Grand Vert, Benzoin Resinoids, Bergamot Essential Oil, Bergamot Oil, Black Pepper Oil, Black Pepper Essence, Black Currant Essence, Blood Orange Oil, Bois des Lands, Brandy Pure Jungle Essence, Cade, Chamomile Romaine, Cardamom Guat Extract, Cardamom Oil, Carrot Heart, Caryophyllene Extract, Cedar, Cedar Leaf, Cedarwood Oil, Cinnamon Bark Ceylon, Cinnamon Ceylon Extract, Beeswax, Citronella, Citronellal, Clary Sage Essential Oil, Clove Leaf Oil Fraction, Copaiba Balsam, Coriander, Cos Anethole, Cos cos essence coriander russianthus, cucumber extract, cumin oil, cypriol heart, elemicool, elemi oil, english white chamomile, eucalyptol, lemon eucalyptus, eugenol, galbanum heart, ginger, grapefruit replacer, guaiac wood oil, glutamic acid oil, healing wood broth, helichrysum, isoeugenol, jasmine sambac, juniper berry oil, key lime, labdanum resinoid, lavandin abrialis oil, lavandin rosso, lavender essential oil, lemon cedra, lemon oil, lemon peel bardery, lemongrass, lemongrass oil, lyssaecube, magnolia flower oil, mandarin oil yellow, menthol crystallize, mint piperita cascade, narcissus, neroli oil, nutmeg, orange flower water, orange oil, orange phase oil, organic rose water, osmanthus, patchouli, patchouli heart, patchouli oil, pepper black oil, peppermint, pelar balsam absolute, petitgrainless, pimento berry oil, pink pepper, raspberry essence, rhodinol, rose, rose centifolia, sandalwood, sichuan pepper extract, styrax white, sweet orange oil, tangerine oil, vanilla, vetiver, violet leaves, violet feuillete, bitter mugwort oil, and combinations thereof.
[0073] In addition to the PRM, the core may contain a pro-perfume that can contribute to improving the longevity of the freshness effect. The pro-perfume may, for example, comprise a non-volatile substance that releases or converts a perfume substance as a result of simple hydrolysis, or it may be a pH-change-triggered pro-perfume (e.g., triggered by a pH drop), or an enzymatically releasable pro-perfume, or a light-triggered pro-perfume. The pro-perfume may exhibit different release rates depending on the pro-perfume selected.
[0074] The core of the encapsulant of the present disclosure may include a core modifier, such as a partitioning modifier and / or a density modifier. In addition to the flavoring, the core may include from greater than 0% to 80%, optionally greater than 0% to 50%, optionally greater than 0% to 30% of the core modifier based on the total weight of the core. Partitioning modifiers include vegetable oils, modified vegetable oils, C4-C 24 The partitioning modifier may include a material selected from the group consisting of mono-, di-, and tri-esters of fatty acids, isopropyl myristate, dodecanophenone, lauryl laurate, methyl behenate, methyl laurate, methyl palmitate, methyl stearate, and mixtures thereof. The partitioning modifier may optionally include or consist of isopropyl myristate. The modified vegetable oil may be esterified and / or brominated. The modified vegetable oil may optionally include castor oil and / or soybean oil. U.S. Patent Application Publication No. 20110268802, incorporated herein by reference, describes other partitioning modifiers that may be useful in the perfume encapsulants described herein.
[0075] ii.Shell The capsules of the present disclosure include a shell surrounding a core.
[0076] The shell may include a first shell component. The shell may optionally include a second shell component surrounding the first shell component. The first shell component may include a condensation layer formed from a condensation product of a precursor. As described in detail below, the precursor may include one or more precursor compounds. The first shell component may include a nanoparticle layer. The second shell component may include an inorganic material.
[0077] The shell may be substantially inorganic (as defined below). The substantially inorganic shell may include a first shell component including a condensed layer surrounding the core, and may further include a nanoparticle layer surrounding the condensed layer. The substantially inorganic shell may further include a second shell component surrounding the first shell component. The first shell component includes an inorganic material, optionally a metal / metalloid oxide, optionally SiO2, TiO2 and Al2O3, and optionally SiO2. The second shell component includes an inorganic material, optionally including a material from the group of materials selected from the list of metal / metalloid oxides, metals, and minerals, optionally SiO2, TiO2, Al2O3, ZrO2, ZnO2, CaCO3, Ca2SiO4, Fe2O3, Fe3O4, clay, gold, silver, iron, nickel, and copper, optionally SiO2 and CaCO3. Optionally, the material of the second shell component is of the same chemical type as the first shell component to maximize chemical compatibility.
[0078] The first shell component may include a condensation layer surrounding the core. The condensation layer may be a condensation product of one or more precursors. The one or more precursors may include at least one compound from the group consisting of Formula (I), Formula (II), and mixtures thereof, where Formula (I) is (M v O z Y n ) w and formula (II) is (M v O z Y n R 1 p ) wThe precursor contains only formula (I) and does not contain compounds according to formula (II) (i.e., R 1 Formulas (I) and (II) are described in more detail below.
[0079] The one or more precursors may be of formula (I): (M v O z Y n ) w (Formula I) In the formula, M is one or more of silicon, titanium, and aluminum; v is the valence number of M and is 3 or 4; z is 0.5 to 1.6, preferably 0.5 to 1.5; and each Y is independently -OH, -OR 2 , -NH2, -NHR 2 , -N(R 2 )2, and R 2 is C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C 22 aryl or a 5-12 membered heteroaryl containing 1-3 ring heteroatoms selected from O, N, and S; R 3 H, C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C 22 aryl, or 5-12 membered heteroaryl containing 1-3 ring heteroatoms selected from O, N, and S, where n is 0.7-(v-1), and w is 2-2000.
[0080] The one or more precursors may be of formula (I), where M is silicon. Y is -OR 2 n may be 1 to 3. Y may be -OR 2 and n is preferably 1 to 3. n is at least 2, and one or more of Y's is -OR 2 and one or more of Y may be -OH.
[0081] R 2is C1~C 20 R may be alkyl. 2 is C6~C 22 R may be aryl. 2 R may be one or more of C1 alkyl, C2 alkyl, C3 alkyl, C4 alkyl, C5 alkyl, C6 alkyl, C7 alkyl, and C8 alkyl. 2 R may be C1 alkyl. 2 R may be C2 alkyl. 2 may be a C3 alkyl. 2 may be a C4 alkyl.
[0082] z may be from 0.5 to 1.3, from 0.5 to 1.1, from 0.5 to 0.9, from 0.7 to 1.5, from 0.9 to 1.3, or from 0.7 to 1.3.
[0083] M is silicon, v is 4, and each Y is -OR 2 where n is 2 and / or 3, and each R 2 may optionally be a C2 alkyl.
[0084] The precursor may include polyalkoxysilane (PAOS). The precursor may include polyalkoxysilane (PAOS) synthesized via a hydrolysis process.
[0085] The precursor may alternatively or additionally comprise one or more compounds of formula (II): (M v O z Y n R 1 p ) w (Formula II) In the formula, M is one or more of silicon, titanium, and aluminum; v is the valence number of M and is 3 or 4; z is 0.5 to 1.6, preferably 0.5 to 1.5; and each Y is independently -OH, -OR 2 ,halogen,
[0086] [ka] -NH2, -NHR 2 , -N(R 2 )2, and
[0087] [ka] Selected from R 2 is C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C 22 aryl, or 5-12 membered heteroaryl containing 1-3 ring heteroatoms selected from O, N, and S; R 3 H, C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C 22 aryl or a 5-12 membered heteroaryl containing 1-3 ring heteroatoms selected from O, N, and S, n is 0-(v-1), and each R 1 are independent, C1~C 30 Alkyl, C1-C 30 Alkylene, C1-C 30 C1-C alkyl substituted with one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl, and heteroaryl; 30 Alkyl or C1-C 30 Alkylene, C1-C substituted with one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl, and heteroaryl; 30 alkylene, p is present in an amount up to pmax, w is 2 to 2000, p is a positive number up to pmax, and pmax=60 / [9 * Mw(R 1 )+8], and Mw(R 1 ) is R 1 is the molecular weight of the group.
[0088] R 1 is a C1-C substituted with 1 to 4 groups independently selected from halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl, and heteroaryl; 30 R may be alkyl. 1 is a C1-C substituted with 1 to 4 groups independently selected from halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl, and heteroaryl; 30 It may be an alkylene.
[0089] As indicated above, it may be preferable to reduce or even eliminate the presence of compounds according to formula (II) having R groups in order to reduce or even eliminate the organic content in the first shell component. The precursor, the condensation layer, the first shell component, and / or the shell may be free of compounds according to formula (II).
[0090] The precursors of formula (I) and / or (II) may be characterized by one or more physical properties, namely molecular weight (Mw), degree of branching (DB) and polydispersity index (PDI) of the molecular weight distribution. It is believed that selecting a particular Mw and / or DB may be useful to obtain capsules that retain their mechanical integrity once resting on a surface and have low shell permeability in a surfactant-based matrix. The precursors of formula (I) and (II) may be characterized as having a DB of 0-0.6, preferably 0.1-0.5, optionally 0.19-0.4, and / or a Mw of 600 Da-100000 Da, preferably 700 Da-60000 Da, optionally 1000 Da-30000 Da. The properties provide useful properties of the precursors to obtain the capsules of the present invention. The precursors of formula (I) and / or (II) may have a PDI of 1-50.
[0091] The condensation layer comprising a metal / semi-metal oxide may be formed from a condensation product of a precursor comprising at least one compound of formula (I) and / or at least one compound of formula (II), optionally in combination with one or more monomeric precursors of the metal / semi-metal oxide, including TiO2, Al2O3 and SiO2, preferably SiO2. The monomeric precursors of the metal / semi-metal oxide include compounds of formula M(Y): V-n R n (wherein M, Y, and R are as defined in formula (II), and n can be an integer from 0 to 3). The monomer precursor of the metal / semi-metal oxide is preferably a compound of the general formula Si(Y) 4-n R n(wherein Y and R are the same as defined in formula (II), and n can be an integer of 0 to 3). Examples of such monomers are TEOS (tetraethoxyorthosilicate), TMOS (tetramethoxyorthosilicate), TBOS (tetrabutoxyorthosilicate), triethoxymethylsilane (TEMS), diethoxy-dimethylsilane (DEDMS), trimethylethoxysilane (TMES), and tetraacetoxysilane (TAcS). These are not meant to limit the scope of monomers that can be used, and it will be clear to one skilled in the art what suitable monomers can be used in combination herein.
[0092] The first shell component may include an optional nanoparticle layer. The nanoparticle layer includes nanoparticles. The nanoparticles of the nanoparticle layer may be one or more of SiO2, TiO2, Al2O3, ZrO2, ZnO2, CaCO3, clay, silver, gold, and copper. Optionally, the nanoparticle layer may include SiO2 nanoparticles.
[0093] The nanoparticles can have an average diameter of from 1 nm to 500 nm, optionally from 50 nm to 400 nm.
[0094] The size of the capsule pores can be adjusted by changing the shape of the nanoparticles and / or by using a combination of nanoparticles of different sizes. For example, non-spherical and irregular nanoparticles can be used as they may improve the packing when forming the nanoparticle layer, thereby resulting in a denser shell structure. This may be advantageous when permeability needs to be limited. The nanoparticles used can have a more regular shape, such as spherical. Any conceivable nanoparticle shape can be used herein.
[0095] The nanoparticles may be substantially free of hydrophobic modifications. The nanoparticles may be substantially free of organic compound modifications. The nanoparticles may include organic compound modifications. The nanoparticles may be hydrophilic.
[0096] The nanoparticles may include surface modifications, examples of which include linear or branched C1-C 20 These surface modifications include, but are not limited to, alkyl groups, surface amino groups, surface methacryl groups, surface halogens, or surface thiols. These surface modifications allow the nanoparticle surface to have organic molecules covalently attached thereto. When inorganic nanoparticles are disclosed herein for use, this means that they may include any or none of the above surface modifications, even if not explicitly listed.
[0097] The capsule of the present disclosure may be defined as having a substantially inorganic shell, including a first shell component and a second shell component. By substantially inorganic, it is meant that the first shell component may include an organic component content of up to 10% by weight or up to 5% by weight, preferably up to 1% by weight, as defined below in the calculation of the organic component content. It may be preferred that the first shell component, the second shell component, or both, in some cases, include an organic component content of about 5% by weight or less, preferably about 2% by weight or less, and optionally about 0% by weight, based on the weight of the first or shell component.
[0098] The first shell component is useful for building a mechanically robust scaffold or skeleton, but can also provide a low shell permeability in liquid products containing surfactants, such as laundry detergents, shower gels, cleansers, etc. (see Surfactants in Consumer Products, J. Falbe, Springer-Verlag). The second shell component can significantly reduce the shell permeability and improve the impermeability of the capsule in a surfactant-based matrix. The second shell component can also significantly improve the mechanical properties of the capsule, such as the burst force and crush strength of the capsule. Without being bound by theory, it is believed that the second shell component contributes to the overall shell densification by depositing precursors in the remaining pores in the first shell component. The second shell component also adds an additional inorganic layer on the surface of the capsule. These improved shell permeability and mechanical properties provided by the second shell component only occur when used in combination with the first shell component, as defined in the present invention.
[0099] A more detailed description of the shell structures, their materials, and how they interact with each other to provide optimal performance can be found in U.S. patent application Ser. Nos. 16 / 851,173, 16 / 851,176, and 16 / 851,194, the disclosures of which are incorporated herein by reference in their entireties.
[0100] iii. Capsule manufacturing process The capsules of the present disclosure may be formed by first mixing a hydrophobic material with any of the above-defined precursors of the condensed layer, thereby forming an oil phase, which may include oil-based and / or oil-soluble precursors. The precursor / hydrophobic material mixture is then used with an aqueous phase as a dispersed phase or as a continuous phase. When the two phases are mixed and homogenized via methods known to those skilled in the art, an O / W (oil-in-water) emulsion is formed in the former case, and a W / O (water-in-oil) emulsion is formed in the latter case. Preferably, an O / W emulsion is formed. The nanoparticles may be present in the aqueous phase and / or the oil phase, regardless of the type of emulsion desired. The oil phase may include an oil-based core conditioning agent and / or an oil-based benefit agent as well as a precursor of the condensed layer. Suitable core materials used in the oil phase are described herein above.
[0101] Once any emulsion is formed, the following steps may occur. (a) Nanoparticles migrate to the oil / water interface, thereby forming a nanoparticle layer. (b) The precursors of the condensation layer, including precursors of metal / metalloid oxides, begin to undergo hydrolysis / condensation reactions with water at the oil / water interface, thus forming a condensation layer surrounded by the nanoparticle layer. The precursors of the condensation layer can further react with the nanoparticles of the nanoparticle layer.
[0102] The precursors forming the condensed layer may be present in an amount of from 1% to 50% by weight, preferably from 10% to 40% by weight, based on the total weight of the oil phase.
[0103] The oil phase composition may include any of the compounds defined in the core section above. The oil phase may contain from 10% to about 99% by weight of the benefit agent, prior to emulsification.
[0104] In the method of making capsules according to the present disclosure, the oil phase may be the dispersed phase and the continuous aqueous (or water) phase may include water, an acid or base, and nanoparticles. The aqueous (or water) phase may have a pH of 1-11, preferably 1-7, at least at the time of mixing both the oil phase and the water phase together. The acid may be a strong acid. The strong acid may include one or more of HCl, HNO3, H2SO4, HBr, HI, HClO4, and HClO3, preferably HCl. The acid may be a weak acid. The weak acid may be acetic acid or HF. The concentration of the acid in the continuous aqueous phase may be between 10 and 1500 mg / kg. -7 The base may be an inorganic base or an organic base, preferably an inorganic base. The inorganic base may be a hydroxide, such as sodium hydroxide and ammonia. For example, the inorganic base may be about 10 -5 M ~ 0.01M NaOH, or about 10 -5 The above list of exemplary acids and bases and their concentration ranges may be in the range of about 1 M to about 1 M ammonia. The above list of exemplary acids and bases and their concentration ranges is not meant to limit the scope of the invention, and other suitable acids and bases that allow for control of the pH of the continuous phase are contemplated herein.
[0105] In the method of making capsules according to the present disclosure, the pH can be varied throughout the process by adding acid and / or base. For example, the method can start with an aqueous phase of acidic or neutral pH, and later on in the process a base can be added to increase the pH. Alternatively, the method can start with an aqueous phase of basic or neutral pH, and later on in the process an acid can be added to decrease the pH. Furthermore, the method can start with an aqueous phase of acidic or neutral pH, and later on in the process an acid can be added to decrease the pH. Still further, the method can start with an aqueous phase of basic or neutral pH, and later on in the process a base can be added to increase the pH. Any suitable pH shift shift can be used. Furthermore, any suitable combination of acid and base can be used at any point in the method to achieve the desired pH. Any of the nanoparticles described above can be used in the aqueous phase. The nanoparticles can be present in an amount of about 0.01% to about 10% by weight, based on the total weight of the aqueous phase.
[0106] The method can include mixing an oil phase and an aqueous phase in a ratio of about 1:10 to about 1:1 oil phase to aqueous phase.
[0107] The second shell component can be formed by mixing the capsules having the first shell component with a solution of a second shell component precursor. The solution of the second shell component precursor can include a water-soluble or oil-soluble second shell component precursor. The second shell component precursor can be one or more of the compounds of formula (I) defined above, tetraethoxysilane (TEOS), tetramethoxysilane (TMOS), tetrabutoxysilane (TBOS), triethoxymethylsilane (TEMS), diethoxy-dimethylsilane (DEDMS), trimethylethoxysilane (TMES), and tetraacetoxysilane (TAcS). The second shell component precursor can also be Si(Y) 4-n R nThe second shell component precursor may include one or more of silane monomers of the type: (wherein Y is a hydrolyzable group, R is a non-hydrolyzable group, and n may be an integer from 0 to 3). Examples of such monomers have been set forth previously in this paragraph, and are not meant to limit the scope of monomers that may be used. The second shell component precursor may include silicates, titanates, aluminates, zirconates, and / or zincates. The second shell component precursor may include carbonates and calcium salts. The second shell component precursor may include salts of iron, silver, copper, nickel, and / or gold. The second shell component precursor may include alkoxides of zinc, zirconium, silicon, titanium, and / or aluminum. The second shell component precursor may include one or more of a silicate solution, such as sodium silicate, a silicon tetraalkoxide solution, iron sulfate and nitrate salts, a titanium alkoxide solution, an aluminum trialkoxide solution, a zinc dialkoxide solution, a zirconium alkoxide solution, a calcium salt solution, and a carbonate solution. The second shell component comprising CaCO3 can be derived from the combined use of a calcium salt and a carbonate salt. The second shell component comprising CaCO3 can be derived from a calcium salt without the addition of carbonate salt by in situ generation of carbonate ions from CO2.
[0108] The second shell component precursor can include any suitable combination of any of the compounds listed above.
[0109] The solution of the second shell component precursor can be added dropwise to the capsule containing the first shell component. The solution of the second shell component precursor and the capsule can be mixed together for 1 minute to 24 hours. The solution of the second shell component precursor and the capsule can be mixed together at room temperature or at an elevated temperature, for example, at a temperature of 20° C. to 100° C.
[0110] The second shell component precursor solution can include the second shell component precursor in an amount of 1% to 50% by weight, based on the total weight of the second shell component precursor solution.
[0111] The capsule having the first shell component can be mixed with a solution of the second shell component precursor at a pH of 1-11. The solution of the second shell precursor can contain an acid and / or a base. The acid can be a strong acid. The strong acid can include one or more of HCl, HNO3, H2SO4, HBr, HI, HClO4, and HClO3, preferably HCl. In other embodiments, the acid can be a weak acid. In embodiments, the weak acid can be acetic acid or HF. The concentration of the acid in the solution of the second shell component precursor can be between 10 and 11. -7 The base may be an inorganic base or an organic base, preferably an inorganic base. The inorganic base may be a hydroxide, such as sodium hydroxide and ammonia. For example, the inorganic base may be about 10 -5 M ~ 0.01M NaOH, or about 10 -5 The acid and base may be from about 1 M to about 1 M ammonia. The list of acids and bases exemplified above is not meant to limit the scope of the invention, and other suitable acids and bases that allow for control of the pH of the second shell component precursor solution are contemplated herein.
[0112] The process of forming the second shell component may include changing the pH during the process. For example, the process of forming the second shell component may start at an acidic or neutral pH and a base may be added later during the process to increase the pH. Alternatively, the process of forming the second shell component may start at a basic or neutral pH and an acid may be added later during the process to decrease the pH. Still further, the process of forming the second shell component may start at an acidic or neutral pH and an acid may be added during the process to further decrease the pH. Still further, the process of forming the second shell component may start at a basic or neutral pH and a base may be added during the process to further increase the pH. Any suitable pH shift may be used. Additionally, any suitable combination of acid and base may be used at any point in the solution of the second shell component precursor to achieve the desired pH. The process of forming the second shell component may include maintaining a stable pH during the process with a deviation of up to ±0.5 pH units. For example, the process of forming the second shell component may be maintained at a basic, acidic, or neutral pH. Alternatively, the process of forming the second shell component may be maintained at a particular pH range by controlling the pH using an acid or a base. Any suitable pH range may be used. Furthermore, any suitable combination of acid and base may be used in the second shell component precursor solution at any time to keep the pH stable in the desired range.
[0113] A more detailed description of the method of making the capsules and the relevant properties of all shell component precursors (i.e., condensation layer precursor, nanoparticles, and second shell component precursor) can be found in U.S. patent application Ser. Nos. 16 / 851173, 16 / 851176, and 16 / 851194, the entire disclosures of which define the method of making the capsules of the present invention.
[0114] Whether making an oil-based or aqueous core, the emulsion can be cured under conditions that solidify the precursors, thereby forming a shell surrounding the core.
[0115] To increase the rate at which solidified capsules are obtained, the reaction temperature for curing can be increased. The curing process can induce condensation of the precursors. The curing process can be carried out at room temperature or at a temperature higher than room temperature. The curing process can be carried out at a temperature between 30°C and 150°C, preferably between 50°C and 120°C, and optionally between 80°C and 100°C. The curing process can be carried out for any suitable period of time to allow the shell of the capsule to be strengthened via condensation of the precursor materials. The curing process can be carried out for a period of 1 minute to 45 days, preferably between 1 hour and 7 days, and optionally between 1 hour and 24 hours. A capsule is considered to be cured when it no longer disintegrates. The determination of capsule disintegration is described in detail below. During the curing step, hydrolysis of the Y moiety (from formula (I) and / or (II)) is believed to occur, followed by subsequent condensation of the -OH group with another -OH group or with another moiety of the Y type (in this case the two Y moieties are not necessarily the same). The hydrolyzed portions of the precursor first condense with surface moieties of the nanoparticles (if the nanoparticles contain such moieties), and as the formation of the shell proceeds, the precursor moieties become reactive with the previously formed shell.
[0116] The emulsion may be cured such that the shell precursors react with the nanoparticles and condense. The following is an example of the hydrolysis and condensation steps described herein for a silica-based shell:
[0117] [Table 1]
[0118] For example, when a precursor of formula (I) or (II) is used, the following describes the hydrolysis and condensation steps:
[0119] [Table 2]
[0120] The capsules may be provided as a slurry composition (or simply "slurry" herein). The result of the methods described herein may be a slurry containing the capsules. The slurry may be formulated into a product, such as, for example, a consumer product.
[0121] The composition may include other perfume capsules. These capsules may be core-shell capsules and may include more than 5% by weight of organic material in the shell relative to the weight of the shell material. Such capsules may be considered "organic" capsules in this disclosure to distinguish them from the inorganic capsules described and claimed herein. The shell material of the organic capsules may include materials, preferably polymeric materials, derived from melamine, polyacrylamide, silicone, polystyrene, polyurea, polyurethane, polyacrylate-based materials, gelatin, styrene maleic anhydride, polyamides, and mixtures thereof. The organic capsules may be coated with a deposition aid, a cationic polymer, a nonionic polymer, an anionic polymer, or a mixture thereof. Suitable deposition polymers may be selected from the group consisting of polyvinyl formaldehyde, partially hydroxylated polyvinyl formaldehyde, polyvinylamine, polyethyleneimine, ethoxylated polyethyleneimine, polyvinyl alcohol, polyacrylates, cationic polysaccharides (e.g., chitosan), and combinations thereof. The organic capsules may have a volume weighted average particle size of from about 0.5 micrometers to about 100 micrometers, preferably from about 1 micrometer to about 60 micrometers, alternatively from about 25 micrometers to about 60 micrometers, optionally from about 25 micrometers to about 60 micrometers.
[0122] Method for treating laundry A process for treating laundry may include providing a laundry article to a washing machine, dispensing a composition comprising a plurality of particles into the washing machine, and contacting the laundry article with the composition during a wash subcycle of the washing machine. The washing machine may have a wash subcycle and a rinse subcycle. About 5 g to about 50 g of the particulate composition may be dispensed into the washing machine.
[0123] By providing scent benefits throughout the wash subcycle, consumers only need to dispense the detergent composition and the composition comprising the particles into a single location, e.g., the wash tub, before or immediately after the start of the washing machine. This may be more convenient for consumers than using a rinse additive composition that is separately dispensed into the wash tub after the wash subcycle is completed, e.g., before, during, or during the rinse cycle. Using the automatic dispensing mechanism of modern upright and highly efficient machines may be inconvenient, since the rinse additive composition must be dispensed in a location other than where the detergent composition is dispensed.
[0124] Optionally, the process may further comprise contacting the clothing item during a wash subcycle of a washing machine with a detergent composition comprising about 3% to about 60% by weight, optionally about 3% to about 40% by weight, of an anionic surfactant. The anionic surfactant may be selected from sulfates, sulfonates, carboxylates, and mixtures thereof. The detergent composition is distinct from the particles. The detergent composition may optionally be provided separately from the particles. The detergent composition may be dispensed separately from a composition comprising a plurality of particles.
[0125] Washing machines have at least two basic subcycles within their operating cycle: a wash subcycle and a rinse subcycle. A washing machine's wash subcycle is a washing machine cycle that begins when the wash tub is initially filled or partially filled with water. The primary purpose of the wash subcycle is to remove or lift soil from the clothing items and suspend the soil in the wash liquor. Typically, the wash liquor is drained at the end of the wash subcycle. A washing machine's rinse subcycle occurs after the wash subcycle and has the primary purpose of rinsing soil, and optionally any benefit agents provided in the wash subcycle, from the clothing items.
[0126] The process may optionally include contacting the clothing items with a detergent composition comprising an anionic surfactant during the wash subcycle. Most consumers provide a detergent composition to the wash tub during the wash subcycle. The detergent composition may include an anionic surfactant and optionally other benefit agents including, but not limited to, perfumes, bleaches, brighteners, hue dyes, enzymes, and the like. During the wash subcycle, the benefit agent provided with the detergent composition is contacted or applied to the clothing items placed in the wash tub. Typically, the benefit agent of the detergent composition is dispersed in the wash liquor of water and benefit agent.
[0127] During the wash subcycle, the wash tub may be filled with water or at least partially filled with water. The individual particles of the composition may dissolve or disperse in water to form a wash liquor containing the components of the particles. Optionally, if a detergent composition is used, the wash liquor may contain the components of the detergent composition and the components of the particles. The particles may be placed in the wash tub of the washing machine before the clothes are placed in the wash tub of the washing machine. The particles may be placed in the wash tub of the washing machine after the clothes are placed in the wash tub of the washing machine. The particles may be placed in the wash tub before filling or partially filling the wash tub with water or after the wash tub has started to fill with water.
[0128] When a consumer uses the detergent composition in carrying out a process of treating a garment, the detergent composition and the particles of the composition can be provided from separate packages. For example, the detergent composition can be a liquid detergent composition provided from a bottle, a sachet, a water-soluble pouch, a dosing cup, a dosing bowl, or a cartridge associated with a washing machine. The particles of the composition can be provided from separate packages, such as, but not limited to, a carton, a bottle, a water-soluble pouch, a dosing cup, a sachet, etc. When the detergent composition is in a solid form, such as a powder, a water-soluble fibrous substrate, a water-soluble sheet, a water-soluble film, a water-soluble film, a water-insoluble fibrous web carrying a solid detergent composition, the particles of the composition can be provided together with the solid detergent composition. For example, the particles of the composition can be provided from a container that contains a mixture of the solid detergent composition and the particles of the composition. The particles of the composition can be provided from a pouch formed with the detergent composition, which is optionally a water-soluble fibrous substrate, a water-soluble sheet, a water-soluble film, a water-soluble film, a water-insoluble fibrous web carrying a solid detergent composition.
[0129] Process for forming particles The particles of the composition can be made by a process that includes multiple steps. The particles can be formed by tableting or melt processing. A melt composition can be prepared that includes about 25% to about 99% by weight of a water-soluble carrier and about 0.1% to about 20% by weight of a capsule.
[0130] Particles of the composition can be formed by using a particle making device 11 (FIG. 1). The molten composition 20 can be prepared in a batch mixer 110 or a continuous mixer 110, or can be prepared on a benchtop by manually mixing the constituent materials. When the carrier is a water-soluble polymer, the water-soluble polymer can be heated to a temperature above the onset of melting of the water-soluble polymer and below the flash point or boiling point of the flavoring in the capsule.
[0131] The molten composition 20, including the water-soluble carrier and capsules, can pass through one or more openings 60 and be deposited as extrudates or droplets 85 onto a moving conveyor 80. The mixture can optionally be deposited in a mold cavity and cooled or allowed to cool to solidify the mixture into particles 90. The particles can be removed from the mold cavity to obtain the finished product. The distributor 30 can be provided with multiple openings. The molten composition 20 can be transported to the distributor via a feed pipe 40. Optionally, a mixer 50, such as a static mixer 55, can be provided in line with the feed pipe 40. Optionally, the feed pipe 40 can be insulated or provided with a heated jacket.
[0132] Optionally, particles 90 can be formed by passing a mixture including the water-soluble carrier and capsules through one or more openings 60 of a dispenser and depositing the mixture on the moving conveyor 80 below the one or more openings 60. The mixture can be solidified to form particles 90. The mixture can be deposited on the moving conveyor 80 as an extrudate, and the extrudate can be cut to form particles 90. Alternatively, the mixture can be passed through one or more openings 60 to form droplets on the moving conveyor 80, and the droplets can be solidified to form particles 90.
[0133] Optionally, a gas supply line can be included upstream of the distributor 30 to include gas in the molten composition. Downstream of the gas supply line, the molten composition 30 can be milled to break up bubbles so that the melt is a gas-entrained melt. The particles formed from the gas-entrained melt can include gas bubbles. The gas supply line and mill can be an integrated unit, a non-limiting example being the OAKES FOAMER (ETOakes Corporation, 686 Old Willets Path, Hauppauge, NY 11788) 2MT1A continuous former. Optionally, gas can be entrained in the molten composition 20 by mixing the molten composition 20 with a gas-generating material.
[0134] particle The particles may each have a mass of about 1 mg to about 500 mg, alternatively about 5 mg to about 500 mg, alternatively about 5 mg to about 200 mg, alternatively about 10 mg to about 100 mg, alternatively about 20 mg to about 50 mg, alternatively about 35 mg to about 45 mg, alternatively about 38 mg. Individual particles have a size of about 0.003 cm 3 ~about 5cm 3 , arbitrarily about 0.003 cm 3 ~about 1cm 3 , arbitrarily about 0.003 cm 3 ~about 0.5cm 3 , arbitrarily about 0.003 cm 3 ~ approx. 0.2cm 3 , arbitrarily about 0.003 cm 3 ~about 0.15cm 3 It is believed that the smaller particles provide better packing of the particles into the container and more rapid dissolution in the wash water. The composition may contain less than 10% by weight of particles having an individual mass of less than about 10 mg. This may reduce the potential for dusting.
[0135] The particles disclosed herein in any of the disclosed embodiments or combinations can have a shape selected from the group consisting of spheres, hemispheres, oblate spheroids, cylinders, polyhedrons, and hemi-oblate spheroids. The particles can be hemispherical, compressed hemispherical, or have at least one substantially flat or planar surface. Such particles can have a relatively large surface area relative to mass compared to spherical particles. The dissolution time in water can decrease as a function of increasing surface area, with shorter dissolution times being preferred over longer dissolution times.
[0136] The particles disclosed herein can have a ratio of maximum dimension to minimum dimension of about 10 to 1, optionally about 8 to 1, optionally about 5 to 1, optionally about 3 to 1, optionally about 2 to 1. The particles disclosed herein can be shaped such that the particles are not flakes. Particles having a ratio of maximum dimension to minimum dimension greater than about 10, or particles that are flakes, tend to be brittle and the particles tend to become powdery. The brittleness of the particles tends to decrease with decreasing values of the ratio of maximum dimension to minimum dimension.
[0137] The particles can comprise about 25% to 99% by weight of the water-soluble carrier and the capsule dispersed in the water-soluble carrier. The particles can be provided at about 0.1% to about 20% by weight of the composition capsule.
[0138] The particles can comprise less than about 20% by weight of anionic surfactant, optionally less than about 10% by weight of anionic surfactant, optionally less than about 5% by weight of anionic surfactant, optionally less than about 3% by weight of anionic surfactant, optionally less than about 1% by weight of anionic surfactant. The particles can comprise 0% to about 20% by weight, optionally 0% to about 10% by weight, optionally about 0% to about 5% by weight, optionally about 0% to about 3% by weight, optionally about 0% to about 1% by weight of anionic surfactant.
[0139] The particles may contain less than about 10% water by weight.
[0140] The particles may include gas bubbles. The gas bubbles may be spherical gas bubbles. Because the particles may include gas bubbles entrained therein, the particles may have a density less than the density or weighted average density of the constituent solid and / or liquid materials forming the particles. It may be advantageous for the particles including gas bubbles to include an antioxidant, since the gas bubbles may contribute to oxidation reactions within the particles. Each particle may have a density of about 1 g / cm 3 Optionally, the particles may each have a density of less than about 0.98 g / cm 3 Optionally, the particles may each have a density of less than about 0.95 g / cm 3 A typical cleaning fluid has a density of about 1 g / cm 3 Therefore, each is about 1g / cm 3 Less than, or even about 0.95 g / cm 3 It may be desirable to provide particles having a density of less than about 1 g / cm individually. 3 Particles having a density less than 90 may be desirable to provide particles 90 that are suspended in the cleaning solution.
[0141] Each particle may have a volume, and the gas occluders within particle 90 may comprise from about 0.5% to about 50% by volume of the particle, or even from about 1% to about 20% by volume of the particle, or even from about 2% to about 15% by volume of the particle, or even from about 4% to about 12% by volume of the particle. Without being bound by theory, it is believed that if the volume of the gas occluders is too large, the particle may not be strong enough to be packaged, shipped, stored, and used without breaking in an undesirable manner.
[0142] The occluders may have an effective diameter of about 1 micrometer to about 2000 micrometers, or even about 5 micrometers to about 1000 micrometers, or even about 5 micrometers to about 200 micrometers, or even about 25 to about 50 micrometers. In general, smaller gas occluders are considered more desirable than larger gas occluders. If the effective diameter of the gas occluder is too large, the particles may not have sufficient strength to be packaged, shipped, stored, and used without breaking in an undesirable manner. The effective diameter is the diameter of a sphere having the same volume as the gas occluder. The gas occluder may be a spherical gas occluder.
[0143] Dryer sheets The capsules can also be used in practice in dryer sheets. The dryer sheets can include a nonwoven fibrous layer and a solid fabric softener composition supported on or within the nonwoven fibrous layer. The fabric softener composition can include a plurality of capsules dispersed in the solid fabric softener composition. The capsules can be as described herein.
[0144] The solid fabric softener composition may comprise a quaternary ammonium compound, optionally an ester quaternary ammonium compound, optionally selected from the group consisting of ditallow, dimethylammonium methylsulfate, N,N-di(oleyl-oxy-ethyl)-N,N-dimethylammonium chloride, N,N-di(canolyl-oxy-ethyl)-N,N-dimethylammonium chloride, N,N-di(oleyl-oxy-ethyl)-N-methyl, N-(2-hydroxyethyl)ammonium methylsulfate ...canolyl-oxy-ethyl)-N,N-dimethylammonium chloride, N,N-di(canolyl-oxy-ethyl)-N,N-dimethylammonium chloride, N,N-di(canolyl-oxy-ethyl)-N,N-dimethylammonium chloride, N,N-di(canolyl-oxy-ethyl)-N,N-dimethylammonium chloride, N,N-di(canolyl-oxy-ethyl)-N,N-dimethylammonium chloride, N,N-di(canolyl-oxy-ethyl)-N,N-dimethylammonium chloride -ethyl)-N-methyl, N-(2-hydroxyethyl)ammonium methyl sulfate-, N,N-di(oleylamidoethyl)-N-methyl, N-(2-hydroxyethyl)ammonium methyl sulfate, N,N-di(2-oleyloxyoxo-ethyl)-N,N-dimethylammonium chloride, N,N-di(2-canolyloxyoxo-ethyl)-N,N-dimethylammonium chloride-, N,N-di(2-oleyloxyethylcarbonyloxyethyl)-N,N-dimethylammonium chloride n-(2-oleyloxyethyl)-N-(2-oleyloxyoxo-ethyl)-N,N-dimethylammonium chloride; n-(2-canolyloxyethyl)-N-(2-canol ...tri(oleyloxyethyl)-N-methylammonium chloride; n-(2-canolyloxyethyl)-N-methylammonium chloride; yi) N-(2-oxy-ethyl)-N-methylammonium chloride-, N-(2-oleyloxyoxoethyl)-N-(oleyl)-N,N-dimethylammonium chloride, N-(2-canolyloxyoxoethyl)-N-(canolyl)-N,N-dimethylammonium chloride, 1,2-dioleyloxy-N,N,N-trimethylammoniopropane chloride, and 5,2-dicanolyloxy-N,N,N-trimethylammoniopropane chloride, and combinations thereof.In one embodiment, the fabric conditioning active is N,N-di(tallowyl-oxy-ethyl)-N-methyl, N-(2-hydroxyethyl)ammonium methyl sulfate, and mixtures thereof, and the fabric softening composition optionally includes a fatty acid.
[0145] The nonwoven fiber material is approximately 10 g / m 2 ~about 50g / m 2 The nonwoven fibrous material may be a spunbond polyester terephthalate, optionally a continuous filament spunbond terephthalate.
[0146] combination Specifically contemplated combinations of the present disclosure are described herein in the following alphabetical sections, which are exemplary in nature and not intended to be limiting.
[0147] A. A composition comprising a plurality of particles, the particles comprising: About 25% by weight to about 99% by weight of a water-soluble carrier; a plurality of capsules dispersed in the water-soluble carrier, the capsules including a core and a shell surrounding the core, the core including a perfume raw material; The shell comprises about 90%-100%, optionally about 95%-100%, optionally about 99%-100% inorganic material by weight of the shell. B. The composition of paragraph A, wherein the inorganic material is selected from metal oxides, semi-metal oxides, metals, minerals, and mixtures thereof, optionally selected from SiO2, TiO2, Al2O3, ZrO2, ZnO2, CaCO3, Ca2SiO4, Fe2O3, Fe3O4, clay, gold, silver, iron, nickel, copper, and mixtures thereof, optionally selected from SiO2, TiO2, Al2O3, CaCO3, and mixtures thereof, and optionally SiO2. C. The composition of paragraphs A or B, wherein the shell comprises a first shell component comprising a condensation layer and a nanoparticle layer, wherein the condensation layer comprises a condensation product of precursors and the nanoparticle layer comprises inorganic nanoparticles, the condensation layer being disposed between the core and the nanoparticle layer, and a second shell component surrounding the first shell component, the second shell component surrounding the nanoparticle layer. D. The capsule is: Average volume weighted capsule diameter of 10mm~200mm, optionally 10mm~190mm; Average shell thickness of 170nm~1000nm, characterized by one or more of a volumetric core to shell ratio of about 50:50 to 99:1, optionally 60:40 to 99:1, optionally 70:30 to 98:2, optionally 80:20 to 96:4; The composition of any of paragraphs A-C, wherein the first shell component comprises an organic content of 5% or less by weight, optionally 2% or less by weight, optionally 0% by weight, based on the weight of the first shell component. E. The shell is: a substantially inorganic first shell component comprising a condensed layer and a nanoparticle layer, the condensation layer comprises a condensation product of a precursor, the nanoparticle layer comprises inorganic nanoparticles; The condensed layer comprises a substantially inorganic first shell component disposed between the core and the nanoparticle layer; an inorganic second shell component surrounding the first shell component, the second shell component includes an inorganic second shell component surrounding the nanoparticle layer; The precursor comprises at least one compound selected from formula (I), formula (II), and mixtures thereof; Formula (I) is (M v O z Y n ) w and Formula (II) is (M v O z Y n R 1p ) w and For formula (I), formula (II), or mixtures thereof, each M is independently selected from silicon, titanium, and aluminum; v is the valence of M and is 3 or 4; z is 0.5 to 1.6; and each Y is independently -OH, -OR 2 ,halogen,
[0148] [ka] -NH2, -NHR 2 , -N(R 2 )2, and
[0149] [ka] is selected from R 2 is C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C 22 aryl, or 5- to 12-membered heteroaryl; The heteroaryl contains 1 to 3 ring heteroatoms selected from O, N, and S; R 3 H, C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C 22 aryl, or 5- to 12-membered heteroaryl; the heteroaryl contains 1 to 3 ring heteroatoms selected from O, N, and S; and w is 2 to 2000; For formula (I), n is 0.7 to (v-1); and In formula (II), n is 0 to (v-1), and each R 1 are independent, C1~C 30 Alkyl, C1-C 30 Alkylene, C1-C 30C1-C alkyl substituted with one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl, and heteroaryl; 30 Alkyl and C1-C 30 Alkylene, C1-C substituted with one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl, and heteroaryl; 30 alkylene; p is a positive number up to pmax, where pmax=60 / [9 * Mw(R 1 )+8], and Mw(R 1 ) is R 1 The composition of any of paragraphs A through D, wherein the molecular weight of the group. F. The composition of paragraph E, wherein the precursor comprises at least one compound according to formula (I). G. The composition of paragraph F, wherein the precursor does not include a compound according to formula (II). H. The composition of paragraph E or F, wherein the precursor comprises at least one compound according to formula (II). I. The plurality of capsules, Average volume-weighted capsule diameter of about 10 mm to about 200 mm; Average shell thickness of about 170 nm to about 1000 nm, a volumetric core-to-shell ratio of about 50:50 to 99:1; The composition of any of paragraphs AH, wherein the first shell component comprises an organic content of about 5% or less by weight, based on the weight of the first shell component. J. A compound of formula (I), formula (II), or both, A polystyrene equivalent weight average molecular weight (Mw) of about 700 Da to about 30,000 Da; Degree of branching from 0.2 to about 0.6 The composition of any of paragraphs E-I, characterized by one or more of: a molecular weight polydispersity index of from about 1 to about 20. The composition of any of paragraphs EJ, wherein KM is silicon. L. The composition of any of paragraphs E-K, wherein for Formula (I), Formula (II), or both Formula (I) and Formula (II), Y is OR and R is selected from a methyl group, an ethyl group, a propyl group, or a butyl group, and optionally an ethyl group. M. The composition of any of paragraphs E-L, wherein the second shell component comprises a material selected from calcium carbonate, silica, and combinations thereof. N. the inorganic nanoparticles of the first shell component comprise at least one of metal nanoparticles, mineral nanoparticles, metal oxide nanoparticles, or semi-metal oxide nanoparticles; Optionally, the inorganic nanoparticles comprise one or more materials selected from SiO2, TiO2, Al2O3, Fe2O3, Fe3O4, CaCO3, clay, silver, gold, or copper; Optionally, the composition of any of paragraphs E-M, wherein the inorganic nanoparticles comprise one or more materials selected from SiO2, CaCO3, Al2O3, and clay. O. The composition of any of paragraphs E-N, wherein the inorganic second shell component comprises at least one of SiO2, TiO2, Al2O3, CaCO3, Ca2SiO4, Fe2O3, Fe3O4, iron, silver, nickel, gold, copper, or clay, optionally at least one of SiO2 or CaCO3, optionally SiO2. P. The composition of any of paragraphs A-O, wherein the water-soluble carrier is a water-soluble polymer. Q. The water-soluble carrier is Formula H-(C2H4O) x -(CH(CH3)CH2O) y -(C2H4O) z -OH (wherein x is 50 to 300, y is 20 to 100, and z is 10 to 200); Formula (C2H4O) q -C(O)O-(CH2)r -CH3 (wherein q is 20 to 200, and r is 10 to 30), Formula HO-(C2H4O) s -(CH2) t -CH3 (wherein s is 30 to 250, and t is 10 to 30), polyethylene glycol aliphatic alcohol ether; C8-C22 alkyl polyalkoxylates containing more than 40 alkoxylate units; Polyethylene glycol having a weight average molecular weight of 2,000 to 15,000; EO / PO / EO block copolymers; PO / EO / PO block copolymers; EO / PO block copolymer; PO / EO block copolymers; Polypropylene glycol; ethoxylated nonionic surfactants having a degree of ethoxylation greater than 30; Polyvinyl alcohol; The composition of any of paragraphs A-P, wherein the polyalkylene glycol is selected from: a polyalkylene glycol having a weight average molecular weight of from 2,000 to 15,000; and mixtures thereof. R. The composition of any of paragraphs A-Q, wherein the water-soluble carrier is a polyethylene glycol having a weight average molecular weight of about 2,000 to about 15,000. S. The composition of any of paragraphs A-R, wherein the water soluble carrier is selected from polyalkylene oxides, polyethylene glycol, sodium acetate, sodium bicarbonate, sodium chloride, sodium silicate, polypropylene glycol polyoxoalkylenes, polyethylene glycol fatty acid esters, polyethylene glycol ethers, sodium sulfate, starch, and mixtures thereof. T. The composition of any of paragraphs A-S, wherein the plurality of capsules is present in a concentration of about 0.1% to about 20% by weight of the composition. U. The composition of any of paragraphs A-T, wherein the particles have at least one flat surface. V. the plurality of particles includes individual particles, and the individual particles have a density of about 1 g / cm 3 less than, optionally about 0.98 g / cm 3 The composition of any of paragraphs A-U, having a density of less than W. The composition of any of paragraphs A-V, wherein the fragrance is a botanical fragrance. X. The carrier is: 0% to 3% by weight of a plasticizer polyol, optionally the plasticizer polyol being liquid at 20° C. and 1 atmosphere; 1% to 20% by weight, optionally 1% to 12% by weight, optionally 6% to 8% by weight of water; 45% to 80% by weight, optionally 50% to 70% by weight, optionally 50% to 60% by weight of a sugar alcohol polyol selected from erythritol, xylitol, mannitol, isomalt, maltitol, lactitol, trehalose, lactose, tagatose, sucralose, and mixtures thereof; The particle is a. a modified starch having a dextrose equivalent of 15 to 20, wherein the sugar alcohol polyol and the modified starch are present in a weight ratio of the sugar alcohol polyol to the modified starch of 2:1 to 16:1, optionally 2:1 to 10:1, optionally 2:1 to 3:1; or b. a modified starch having a dextrose equivalent of 4 to less than 15, wherein the sugar alcohol polyol and the modified starch are present in a weight ratio of the sugar alcohol polyol to the modified starch of 1.5:1 to 16:1, optionally 1.5:1 to 10:1, optionally 1.5:1 to 4:1; The composition of any of paragraphs A-W, wherein the capsules, the water, and the sugar alcohol polyol are dispersed in the modified starch. Y. The composition of paragraph X, wherein the modified starch has a dextrose equivalent of 15 to 20, and the sugar alcohol polyol and the modified starch are present in a ratio of 2:1 to 16:1, optionally 2:1 to 10:1, optionally 2:1 to 3:1. Z. The composition of paragraph X, wherein the modified starch has a dextrose equivalent of from 4 to less than 15, and the sugar alcohol polyol and the modified starch are present in a weight ratio of the sugar alcohol polyol to the modified starch of from 1.5:1 to 16:1, optionally from 1.5:1 to 10:1, optionally from 1.5:1 to 4:1. AA. The composition of paragraph Z, wherein the modified starch has a dextrose equivalent of 4 to 12. BB. The composition of any of paragraphs X-AA, wherein the modified starch is maltodextrin. CC. The composition of any of paragraphs X-BB, wherein the sugar alcohol polyol is mannitol. DD. The carrier is: 0% to 3% by weight of a plasticizer polyol that is liquid at 20° C. and 1 atmosphere; 1% to 10% by weight, optionally 3% to 8% by weight, of water; 15% to 40% by weight, optionally 20% to 30% by weight, of a sugar alcohol polyol selected from erythritol, xylitol, mannitol, isomalt, maltitol, lactitol, trehalose, lactose, tagatose, sucralose, and mixtures thereof; a modified starch having a dextrose equivalent of 4 to less than 15, wherein the sugar alcohol polyol and the modified starch are present in a weight ratio of the sugar alcohol polyol to the modified starch of 1:5 to 1:1; the capsules, the water, and the sugar alcohol polyol are dispersed in the modified starch; The composition of any of paragraphs A-W, wherein the particles each have an outer surface and the anti-caking agent is on the outer surface. EE. A process for treating laundry comprising: providing laundry items to a washing machine; dispensing the plurality of particles of any of paragraphs A-DD into the washing machine; contacting the laundry article with the plurality of particles during a wash subcycle of the washing machine. FF. The process of paragraph EE, further comprising the step of dispensing into said washing machine a laundry detergent comprising from about 3% to about 60% by weight of an anionic or nonionic surfactant. GG. The process of paragraphs EE or FF, wherein about 5 g to about 50 g of the plurality of particles is dispensed into the washing machine. HH. A process for forming a plurality of particles of any of paragraphs A-DD, comprising: providing a molten composition comprising the water-soluble carrier and the capsule; passing the molten composition through one or more openings in a dispenser; depositing the molten composition on a movable conveyor beneath the one or more openings. II. A nonwoven fiber layer; a solid fabric softener composition supported on or within the nonwoven fibrous layer; The solid fabric softener composition comprises a plurality of capsules dispersed in the solid fabric softener composition, the capsules comprising a core and a shell surrounding the core, the core comprising a perfume raw material; The shell comprises about 90% to 100%, optionally about 95% to 100%, optionally about 99% to 100%, by weight of the shell, of inorganic material. JJ. The dryer sheet of paragraph II, wherein the inorganic material is selected from metal oxides, semi-metal oxides, metals, minerals, and mixtures thereof, optionally selected from SiO2, TiO2, Al2O3, ZrO2, ZnO2, CaCO3, Ca2SiO4, Fe2O3, Fe3O4, clay, gold, silver, iron, nickel, copper, and mixtures thereof, optionally selected from SiO2, TiO2, Al2O3, CaCO3, and mixtures thereof, and optionally SiO2. KK. The dryer sheet of paragraph II or JJ, wherein the shell includes a first shell component comprising a condensation layer and a nanoparticle layer, the condensation layer comprising a condensation product of precursors and the nanoparticle layer comprising inorganic nanoparticles, the condensation layer being disposed between the core and the nanoparticle layer, and a second shell component surrounding the first shell component, the second shell component surrounding the nanoparticle layer. LL. The shell is a substantially inorganic first shell component comprising a condensed layer and a nanoparticle layer, the condensation layer comprises a condensation product of a precursor, the nanoparticle layer comprises inorganic nanoparticles; The condensed layer comprises a substantially inorganic first shell component disposed between the core and the nanoparticle layer; an inorganic second shell component surrounding the first shell component, the second shell component includes an inorganic second shell component surrounding the nanoparticle layer; The precursor comprises at least one compound selected from formula (I), formula (II), and mixtures thereof; Formula (I) is (M v O z Y n ) w and Formula (II) is (M v O z Y n R 1 p ) w and For formula (I), formula (II), or mixtures thereof, each M is independently selected from silicon, titanium, and aluminum; v is the valence of M and is 3 or 4; z is 0.5 to 1.6; and each Y is independently -OH, -OR 2 ,halogen,
[0150] [ka] -NH2, -NHR2 , -N(R 2 )2, and
[0151] [ka] is selected from R 2 is C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C 22 aryl, or 5- to 12-membered heteroaryl; The heteroaryl contains 1 to 3 ring heteroatoms selected from O, N, and S; R 3 H, C1~C 20 Alkyl, C1-C 20 Alkylene, C6~C 22 aryl, or 5- to 12-membered heteroaryl; the heteroaryl contains 1 to 3 ring heteroatoms selected from O, N, and S; and w is 2 to 2000; For formula (I), n is 0.7 to (v-1); and In formula (II), n is 0 to (v-1), and each R 1 are independent, C1~C 30 Alkyl, C1-C 30 Alkylene, C1-C 30 C1-C alkyl substituted with one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl, and heteroaryl; 30 Alkyl and C1-C 30 Alkylene, C1-C substituted with one or more of halogen, -OCF3, -NO2, -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO2H, CO2 alkyl, aryl, and heteroaryl; 30 alkylene; p is a positive number up to pmax, where pmax=60 / [9 *Mw(R 1 )+8], and Mw(R 1 ) is R 1 The dryer sheet of any of paragraphs II through KK, wherein the molecular weight of the group is MM. The solid fabric softener composition comprises a quaternary ammonium compound, optionally an ester quaternary ammonium compound, optionally selected from the group consisting of ditallow, dimethylammonium methylsulfate, N,N-di(oleyl-oxy-ethyl)-N,N-dimethylammonium chloride, N,N-di(canolyl-oxy-ethyl)-N,N-dimethylammonium chloride, N,N-di(oleyl-oxy-ethyl)-N-methyl, N-(2-hydroxyethyl)ammonium methylsulfate, N,N-di(canolyl-oxy-ethyl)- N-methyl, N-(2-hydroxyethyl)ammonium methyl sulfate-, N,N-di(oleylamidoethyl)-N-methyl, N-(2-hydroxyethyl)ammonium methyl sulfate, N,N-di(2-oleyloxyoxo-ethyl)-N,N-dimethylammonium chloride, N,N-di(2-canolyloxyoxo-ethyl)-N,N-dimethylammonium chloride-, N,N-di(2-oleyloxyethylcarbonyloxyethyl)-N,N-dimethylammonium chloride, N,N-di( 2-Canolyloxyethylcarbonyloxyethyl)-N,N-dimethylammonium chloride; N-(2-oleyloxyethyl)-N-(2-oleyloxyoxo-ethyl)-N,N-dimethylammonium chloride; N-(2-canolyloxyethyl)-N-(2-canolyloxyoxo-ethyl)-N,N-dimethylammonium chloride; N,N,N-tri(oleyloxyethyl)-N-methylammonium chloride; N,N,N-tri(canolyloxyethyl)-N-methylammonium chloride 11. The dryer sheet of any of paragraphs II through LL, wherein the dryer sheet is selected from the group consisting of N-(2-oleyloxyoxoethyl)-N-(oleyl)-N,N-dimethyl ammonium chloride, N-(2-canolyloxyoxoethyl)-N-(canolyl)-N,N-dimethyl ammonium chloride, 1,2-dioleyloxy-N,N,N-trimethylammoniopropane chloride, and 5,2-dicanolyloxy-N,N,N-trimethylammoniopropane chloride, and combinations thereof.In one embodiment, the fabric conditioning active is N,N-di(tallowyl-oxy-ethyl)-N-methyl, N-(2-hydroxyethyl)ammonium methyl sulfate, and mixtures thereof, and the fabric softening composition optionally includes a fatty acid. NN. The nonwoven fibrous material has a density of about 10 g / m 2 ~about 50g / m 2 The dryer sheet of any of paragraphs II-MM, having a basis weight of OO. The dryer sheet of any of paragraphs II-NN, wherein the nonwoven fibrous material is a spunbond polyester terephthalate, optionally a continuous filament spunbond terephthalate.
[0152] Test Method It will be understood that the test methods disclosed in the Test Methods section of this application should be used to measure the values of each of the parameters of Applicant's claimed subject matter claimed and described herein.
[0153] i. Partition coefficient method The partition coefficient P is the concentration ratio of a compound in a mixture of two immiscible phases (in this case n-octanol / water) at equilibrium. The log value of the n-octanol / water partition coefficient (logP) can be experimentally measured using well-known means such as the "shake flask" method (described, for example, in "The Measurement of Partition Coefficient", Molecular Informatics, Volume 7, Issue 3, 1988, Pages 133-144, Dearden JC, Bresnan) that measures the distribution of solutes by UV / VIS spectroscopy. Alternatively, logP can be calculated for each PRM in the fragrance mixture to be tested. The logP values of individual PRMs are preferably calculated using the Consensus logP Computational Model, version 14.02 (Linux), available from Advanced Chemistry Development Inc. (ACD / Lab) (Toronto, Canada), resulting in unitless logP values. The ACD / Labs Consensus logP Computational Model is part of the ACD / Labs model suite.
[0154] ii. Average shell thickness measurement The capsule shell, including the first shell component and, if present, the second shell component, is measured in nanometers for 20 delivery capsules containing beneficial agent using a Focused Ion Beam Scanning Electron Microscope (FIB-SEM, FEI HELIOS NANOLAB 650) or equivalent instrument. Samples are prepared by diluting (1:10) a small amount of liquid capsule dispersion (20 ML) with distilled water. The suspension is then deposited on an ethanol-cleaned aluminum stub and transferred to a carbon coating device (LEICA EM ACE600 or equivalent instrument). The samples are dried under vacuum in the coating device (vacuum level: 10 -5mbar). 25 nm to 50 nm of carbon is then flash deposited onto the sample to deposit a conductive carbon layer on its surface. The aluminum stub is then transferred to the FIB-SEM and a cross section of the capsule is prepared. Using a cross section cleaning pattern, cross sections are prepared by ion milling with an emission current of 2.5 nA at an accelerating voltage of 30 kV. Images are acquired at 5.0 kV and 100 pA using immersion mode (dwell time: approximately 10 microseconds) at a magnification of approximately 10,000x.
[0155] Images of the crushed shells are obtained in cross-section from 20 randomly selected benefit agent delivery capsules with no size bias to create a representative sample of the size distribution of capsules present. The shell thickness of each of the 20 capsules is measured at three different randomly selected locations using calibrated microscope software by drawing a measurement line perpendicular to the tangent plane of the outer surface of the capsule shell. Sixty independent thickness measurements are recorded and used to calculate the average thickness.
[0156] iii. Mean and coefficient of variation of volume-weighted capsule diameter The capsule size distribution is determined by single-particle optical sensing (SPOS), also called optical particle counting (OPC), using an ACCUSIZER 780 AD instrument or equivalent and accompanying software CW788 version 1.82 (Particle Sizing Systems, Santa Barbara, California, USA) or equivalent. The instrument is configured with the following conditions and options: flow rate = 1 mL / sec; small diameter threshold = 0.50 Mm; sensor model number = LE400-05SE or equivalent; autodilution = on; collection time: 60 seconds; number of channels = 512; reservoir fluid volume = 50 mL; maximum coincidence count = 9200. The measurement is started by cold-conditioning the sensor by flushing with water until the background count is less than 100. A sample of the delivery capsules in suspension is introduced and the capsule density adjusted, if necessary, via automatic dilution with deionized water to give a maximum capsule count of 9200 per mL. The suspension is analyzed for 60 seconds. The size range used was 1 mm to 493.3 mm.
[0157] Volume distribution:
[0158]
number
[0159]
number
[0160] iv. Evaluation of volumetric core-to-shell ratio The value of the volumetric core-to-shell ratio is determined as follows and is dependent on the average shell thickness as measured by the Shell Thickness Test Method. The volumetric core-to-shell ratio of a capsule having a measured average shell thickness is calculated by the following equation:
[0161]
number
[0162] This ratio can be converted to a core to shell fraction value by calculating the core weight percentage using the following formula:
[0163]
number
[0164] Method for determining branching degree The branching degree of the precursor was determined as follows: The branching degree is measured using (29Si) nuclear magnetic resonance spectroscopy (NMR).
[0165] a. Sample preparation Each sample is diluted to a 25% solution using deuterated benzene (Benzene-D6 "100%" (D, 99.96%, available from Cambridge Isotope Laboratories Inc., Tewksbury, MA) or equivalent. 0.015 M chromium(III) acetylacetonate (99.99% purity, available from Sigma-Aldrich, St. Louis, MO) or equivalent) is added as a paramagnetic relaxation reagent. If glass NMR tubes (Wilmad-LabGlass, Vineland, NJ or equivalent) are used for the analysis, a blank sample should also be prepared by filling the NMR tube with the same type of deuterated solvent used to dissolve the sample. The same glass tube should be used to analyze the blank and the sample.
[0166] b. Analysis of the samples The degree of branching is determined using a BRUKER 400 MHz nuclear magnetic resonance spectroscopy (NMR) instrument, or equivalent. A standard silicon (29Si) method (e.g., from Bruker) is used with default parameter settings, with a minimum of 1000 scans and a relaxation time of 30 seconds.
[0167] c. Sample processing Samples are stored and processed using system software appropriate for NMR spectroscopy, such as MESTRENOVA version 12.0.4-22023 (available from Mestrelab Research) or equivalent. Phase adjustment and background correction are applied. There is a large, broad signal extending from -70 to -136 ppm, which is a result of using glass NMR tubes as well as the glass present in the probe housing. This signal is suppressed by subtracting the spectrum of the blank sample from that of the synthetic sample, provided that the same tube and the same method parameters are used to analyze the blank and sample. To further account for slight differences in data collection, tubes, etc., the area outside the peak of interest should be integrated and normalized to a consistent value. For example, integrate from -117 to -115 ppm and set the integration value to 4 for all blanks and samples.
[0168] The resulting spectrum produces up to five main peak regions. The first peak (Q0) corresponds to unreacted TAOS. The second set of peaks (Q1) correspond to the end groups. The next set of peaks (Q2) correspond to the linear groups. The next set of broad peaks (Q3) are the semi-dendritic units. The final set of broad peaks (Q4) are the dendritic units. When PAOS and PBOS are analyzed, each group falls within a defined ppm range. Representative ranges are listed in Table 1 below.
[0169] [Table 3]
[0170] Polymethoxysilanes have different chemical shifts for Q0 and Q1, overlapping signals for Q2, and Q3 and Q4 are unchanged, as shown in Table 2 below.
[0171] [Table 4]
[0172] The ppm ranges shown in the table above may not apply to all monomers, however other monomers may give rise to different chemical shifts, but the proper assignment of Q0-Q4 should not be affected.
[0173] Using MESTRENOVA, each peak group can be integrated and the degree of branching calculated by the following formula:
[0174]
number
[0175] d. Method for determining molecular weight and polydispersity index The molecular weight (weight average molecular weight (Mw) in terms of polystyrene) and polydispersity index (Mw / Mn) of the condensation layer precursors described herein are determined using size exclusion chromatography with refractive index detection, where Mn is the number average molecular weight.
[0176] Sample preparation The sample is weighed and then diluted to a target concentration of 10 mg / mL with the solvent used in the instrument system. For example, 50 mg of polyalkoxysilane is weighed into a 5 mL volumetric flask, dissolved, and diluted to a given volume with toluene. After the sample is dissolved in the solvent, it is passed through a 0.45 Mm nylon filter and loaded into the instrument's autosampler.
[0177] Analysis of samples An HPLC system using an autosampler (e.g., Waters, Milford Mass., WATERS 2695 HPLC Separation Module, or equivalent) connected to a refractive index detector (e.g., WYATT, Santa Barbara, Calif., 2414 Refractive Index Detector, or equivalent) is used for polymer analysis. Separation is performed on three columns, each 7.8 mm ID x 300 mm long, packed with 5 Mm of polystyrene-divinylbenzene media, connected in series, with molecular weight cutoffs of 1, 10, and 60 kDA, respectively. Suitable columns are TSKGEL G1000HHR, G2000HHR, and G3000HHR columns (available from TOSOH Bioscience, King of Prussia, Pa.) or equivalent. A 5 mm polystyrene-divinylbenzene guard column (e.g., TSKGEL Guardcolumn HHR-L (TOSOH BIOSCIENCE), or equivalent), 6 mm ID x 40 mm length, is used to protect the analytical column. Toluene (HPLC grade or equivalent) is pumped uniformly at 1.0 mL / min with both the column and detector maintained at 25° C. 100 mL of prepared sample is injected for analysis. Sample data is stored and processed using software with GPC calculation capabilities (e.g., ASTRA Version 6.1.7.17 software or equivalent available from Wyatt Technologies, Santa Barbara, Calif.).
[0178] The system is calibrated using 10 or more narrowly dispersed polystyrene standards with known molecular weights ranging from about 0.250-70 kDa (e.g., Standard READYCAL Set, e.g., Sigma-Aldrich, PN76552, or equivalent) using a third-order fit to the Mp vs. retention time curve.
[0179] The system software is used to calculate and report the weight average molecular weight (Mw) and polydispersity index (Mw / Mn).
[0180] v. Method for calculating organic content in the first shell component As used herein, the definition of organic moieties in the inorganic shell of the capsule according to the present disclosure: Any moiety X that cannot be cleaved from the metal precursor bearing the metal M under the specified reaction conditions via hydrolysis of the MX bond (M belongs to the metal and metalloid group and X belongs to the non-metal group, linking the moiety to the inorganic precursor of the metal or metalloid M) is considered as an organic moiety. The reaction conditions set forth above are that it has a minimum degree of hydrolysis of 1% when exposed to distilled water with neutral pH without stirring for 24 hours.
[0181] This method allows the theoretical organic content to be calculated, assuming complete conversion of all hydrolyzable groups. It therefore becomes possible to evaluate the theoretical proportion of organic components for any mixture of silanes, the result of which represents only the organic content of this precursor mixture itself, and not the actual organic content in the first shell component. Therefore, if a specific percentage for the organic content of the first shell component is disclosed anywhere in this document, that percentage should be understood as containing any mixture of unhydrolyzed or prepolymerized precursors that gives a theoretical organic content smaller than the disclosed number according to the following calculation.
[0182] The example calculation immediately follows for silane, followed by calculations for the general case.
[0183] Each mole fraction Y i Consider a mixture of silanes having the formula: where i is the identification number of each silane. The mixture can be represented as: Si(XR) 4-n R n where XR is a group hydrolyzable under the conditions described above, and R i ni is non-hydrolyzable under the above conditions, and n i =0, 1, 2, or 3.
[0184] Such a mixture of silanes results in a shell having the general formula:
[0185]
number
[0186] The weight percentage of the organic moieties, as defined above, can then be calculated as follows: 1) Find the mole fraction of each precursor (including nanoparticles). 2) Determine the general formula for each precursor (including nanoparticles). 3) Calculate the general formula for the mixture of precursors and nanoparticles based on the mole fractions. 4) Conversion to reacted silane (all hydrolyzable groups to oxygen groups). 5) Calculate the weight ratio of organic moieties to the total mass (assuming 1 mole of Si per framework).
[0187] An example calculation is shown in FIG.
[0188] [Table 5]
[0189] To calculate the general formula of a mixture, the indices of each atom in the individual formulas are multiplied by their respective mole fractions. Then, in the case of a mixture, when similar indices occur, the sum of the fractional indices is taken (typically for the ethoxy groups).
[0190] Note: The sum of all Si fractions will always sum to 1 in the mixture general formula due to the calculation method (total mole fractions of Si sum to 1).
[0191]
number
[0192] To convert the unreacted formula to the reacted formula, simply divide all the hydrolyzable group indices by 2 and then add them together (along with any existing oxygen groups, if applicable) to get the fully reacted silane. SiO 1.88 Me 0.20
[0193] In this case, the expected result is SiO since the sum of all the exponents must follow the formula: 1.9 Me 0.2 Is: A+B / 2=2, In the formula, A is the oxygen atom index and B is the sum of all non-hydrolyzable indexes. Small errors arise from taking round numbers in the calculation, which should be corrected. Then, readjust the oxygen atom index to satisfy this formula.
[0194] Therefore, the final formula is SiO 1.9 Me 0.2 and the weight ratio of the organic component is calculated as follows: Weight ratio:=(0.20 * 15) / (28+1.9 * 16+0.20 * 15)=4.9%
[0195] General case The above formula can be generalized by considering the valence of the metal or metalloid M, thus obtaining the following modified formula: M(XR) V-ni R i ni A similar method is used, but the valence V of each metal is taken into account. EXAMPLES
[0196] The examples provided below are intended to be illustrative and not limiting in nature.
[0197] Example 1. Synthesis of non-hydrolyzable precursors 1000 g of tetraethoxysilane (TEOS, available from Sigma Aldrich) was added to a clean, dry round bottom flask equipped with a stir bar and distillation apparatus under nitrogen atmosphere. 490 mL of acetic anhydride (available from Sigma Aldrich) and 5.8 g of tetrakis(trimethylsiloxy)titanium (available from Gelest) were added and the contents of the flask were stirred at 135° C. for 28 hours. During this time, ethyl acetate produced by the reaction of the ethoxysilane groups with acetic anhydride was distilled off. The reaction flask was cooled to room temperature and placed on a rotary evaporator (BUCHI Rotovapor R110) which was used with a water bath and a vacuum pump (WELCH 1402 DuoSeal) to remove all remaining solvents and volatile compounds. The resulting polyethoxysilane (PEOS) was a yellow viscous liquid with the following specifications as seen in Table 4: The ratio of TEOS to acetic anhydride can be varied to control the parameters shown in Table 4.
[0198] [Table 6]
[0199] Example 2. Silica shell-based fragrance capsule The oil phase was prepared by mixing and homogenizing the precursor with the benefit agent and / or core modifier (1 part non-hydrolyzable precursor to 2 parts benefit agent and / or core modifier). The water phase was prepared by adding 1.25 wt% Aerosil 300 (available from Evonik) in 0.1M HCl aqueous solution and dispersed in an ultrasonic bath for at least 30 minutes. Once each phase was prepared separately, they were combined (1 part oil to 4 parts water) and the oil phase was dispersed in the water phase using an IKA ULTRATURRAX S25N-10G mixing tool at 13400 RPM / 1 min. Once the emulsification process was complete, the resulting emulsion was cured with the following temperature profile: 22°C for 4 hours, 50°C for 16 hours, and 70°C for 96 hours. To attach the second shell component, the capsules undergo post-treatment with the second shell component solution: the slurry is diluted 2-fold in 0.1 M HCl and treated with controlled addition (40 ML / min, 0.16 mL / g of slurry) of 10 wt. % aqueous sodium silicate solution using a suspended magnetic stirrer reactor at 22° C. and 250 RPM. The pH was kept constant at pH 7 using 1 M HCl (aq). After the injection of the second shell component solution was finished, the capsules were centrifuged at 2500 rpm for 10 minutes and redispersed in deionized water. The capsule population had an average size of 29.22 mm and a CoV of 38%.
[0200] FIG. 2 shows a schematic diagram of a method for making a capsule 8 having a first shell component 6 prepared with a hydrophobic core 4. For example, in a first box 100, an oil phase 1 is provided to an aqueous phase 2. The oil phase 2 contains a hydrophobic benefit agent, such as one or more perfume raw materials, and a liquid precursor material. Nanoparticles 3 surround the oil phase 1, forming, for example, a Pickering emulsion. In a second box 101, hydrolyzed precursors 5 begin to form at the interface around the core 4, which contains the oil phase including the benefit agent. In a third box 102, a first shell component 6 is formed around the core 4, the first shell component being formed from the nanoparticles 3 and the hydrolyzed precursors 5.
[0201] Figure 3 shows a schematic diagram of a capsule 9 in a box 103 having a shell 10, which has a first shell component 6 and a second shell component 7 around a core 4. The capsule 9 is shown in an aqueous phase 2. The core 4 contains one or more perfume raw materials. Figure 4 shows a scanning electron microscope image of a cross section of such a capsule 9. The core 4 is surrounded by a shell 10, which contains a first shell component 6 surrounded by a second shell component 7.
[0202] FIG. 5 shows a scanning electron microscope image of a population of silica shell based fragrance capsules described in this disclosure.
[0203] Example 3. Exemplary particle formulations Two unique samples of particles were prepared, one containing silica shell-based perfume capsules (Inventive Example 3A) and the other containing polyacrylate shell-based perfume capsules (Comparative Example 3B). The general procedure for preparing the particles involves setting a hot plate to a temperature of 85° C., weighing a beaker on the hot plate, allowing the contents to come to the correct temperature, then manually pipetting the mixture into a mold to create uniformly sized particles, and allowing to cool. The individual particles thus formed were sized such that four of such particles weighed approximately 0.140-0.145 g. The composition of the two particles is shown in Table 5 below.
[0204] Inventive Example 3A below (Table 5) was a population of perfume capsules prepared by encapsulating a mixture of perfume raw materials "Perfume 1" according to Table 5 below. The capsules in this population included a silica-based first shell component and a second shell component according to the present disclosure.
[0205] Comparative Example 3B below (Table 5) was a population of perfume capsules comprising a polyacrylate shell encapsulating the same mixture of perfume raw materials ("Perfume 1") with an encapsulant made according to the process disclosed in WO 2020 / 117996.
[0206] [Table 7]
[0207] Inventive Example 3A and Comparative Example 3B were tested under use conditions with fabrics to determine wet fabric headspace and dry fabric headspace. A MIELE HONEYCOMB CARE W1724 washing machine was used with cycle settings of 30°C, 1000 RPM, 30 minutes, express cycle program. The fabrics used for testing were 420g of terry cotton test fabric. Each of the 14 pieces of terry cotton test fabric was 30cm x 15cm and had a mass of 30g. The test also included a ballast load. The ballast load was 1369g of Calderon cotton (10 pieces) and 1220g of Calderon polyester cotton (10 pieces). Each of the 10 pieces of Calderon cotton was 52cm x 42cm and had a mass of 137g. Each of the 10 pieces of Calderon polyester cotton was 46cm x 46cm and had a mass of 122g. The particulates and liquid detergent were delivered to the machine drum at the specified levels, i.e., 9 g of particulates at the bottom of the drum prior to loading the fabrics, and 58.47 g of the liquid detergent formulation in Table 6 below. The liquid detergent was dosed onto the fabrics. After washing, a sample of the terry cotton test fabric was obtained for wet fabric headspace testing, and the remainder of the terry cotton test fabric was line dried at controlled temperature and humidity (22° C. / 50% rH) every 24 hours.
[0208] [Table 8]
[0209] Perfume headspace analysis was performed on terry cotton test fabrics immediately after the wash cycle while they were still wet (Wet Fabric Headspace, WFHS). Six 4 cm x 4 cm samples of terry cotton test fabrics were analyzed by fast headspace GC / MS for each wash test. Each 4 x 4 cm sample of terry cotton test fabric was transferred to a 25 mL headspace vial. The terry cotton test fabric samples were equilibrated at 65°C for 10 minutes. The headspace above the terry cotton test fabric samples was sampled by SPME (50 / 30 Mm DVB / Carboxen / PDMS) technique for 5 minutes. The SPME fibers were then thermally desorbed on-line into the GC. The analytes were analyzed in full scan mode on the fast GC / MS. The total headspace response (expressed in nmol / L) was determined by ion extraction of the specific masses of the perfume raw materials. The terry cotton test fabrics were line dried for 24 hours at controlled temperature and humidity (22°C / 50%rH) and then the dry terry cotton test fabrics were tested in the same manner, with the only difference being that the terry cotton test fabrics were dry instead of wet (Dry Fabric Headspace, DFHS).
[0210] The particles of inventive Example 3A and comparative Example 3B each provided the same mass of perfume. For each individual perfume raw material, the wet fabric headspace (WFHS) and dry fabric headspace (DFHS) were measured. For each perfume raw material, the ratio of WFHS / DFHS was calculated (see Table 7). The relative standard deviation of WFHS / DFHS was also calculated for inventive Example 3A and comparative Example 3B. As shown in Figure 6 (box plot showing the center line, the first and third quartiles at the edge of the box, and the maximum and minimum whiskers), the capsule according to inventive Example 3A had a lower relative standard deviation of headspace ratio compared to comparative Example 3B. This indicates a more consistent perfume profile between wet and dry fabric for the capsule of inventive Example 3A compared to comparative Example 3B.
[0211] [Table 9]
[0212] Example 4. Exemplary particle formulations are shown in Table 8 below.
[0213] [Table 10]
[0214] Example 5 Non-hydrolyzable PEOS synthesis: 1000 g of TEOS (available from Sigma Aldrich) was added to a clean, dry round-bottom flask equipped with a stir bar and distillation apparatus under a nitrogen atmosphere. 564 g of acetic anhydride (available from Sigma Aldrich) and 5.9 g of tetrakis(trimethylsiloxide)titanium (Gelest, available from Sigma Aldrich) were then added and the contents of the flask were heated to 135° C. with stirring. The reaction temperature was maintained at 135° C. for 30 hours with vigorous stirring, during which time organic esters formed by the reaction of alkoxysilane groups with acetic anhydride were distilled off along with additional organic esters formed by the condensation of other alkoxysilane groups with silyl-acetate groups generated as polyethoxysilane (PEOS) was produced. The reaction flask was cooled to room temperature and placed on a rotary evaporator (Buchi Rotovapor R110) which was used with a water bath and a vacuum pump (WELCH 1402 DUOSEAL) to remove any remaining solvent. The branching degree (DB), molecular weight (Mw), and polydispersity index (PDI) of the synthesized PEOS polymer were 0.42, 2.99, and 2.70, respectively.
[0215] Capsule synthesis: Five batches were made according to the following procedure, and after the curing process, the five batches were combined to obtain a combined slurry. The oil phase was prepared by mixing and homogenizing (or even dissolving, if all compounds are miscible) 3g of the PEOS precursor synthesized above with 2g of benefit agent and / or core modifier, here fragrance oil. 100g of the water phase was prepared by mixing 0.5g of NaCl, 3.5g of AEROSIL 300 fumed silica from EVONIK, and 96g of DI water. The fumed silica was dispersed in the water phase using an IKA ULTRA-TURRAX (S25N) at 20000RPM for 15 minutes. Once each phase was prepared separately, 5g of the oil phase was dispersed into 16g of the water phase using an IKA ULTRA-TURRAX mixer (S25N-10g) at 25000 RPM for 5 minutes to reach the desired average oil droplet diameter. 0.1M HCl was then added dropwise to bring the pH to 1. Once the emulsification process was complete, the resulting emulsion was left unstirred at room temperature for 4 hours, then at 90°C for 16 hours until sufficient hardening had occurred to prevent the capsules from collapsing. The five batches were combined after the hardening process to obtain a combined capsule slurry.
[0216] To attach the second shell component, the combined capsule slurry was post-treated with the second shell component solution. 50 g of the combined slurry was diluted with 50 g of 0.1 M HCl(aq). 1 M NaOH(aq) was added dropwise to adjust the pH to 7. The diluted slurry was then treated at room temperature with the controlled addition (40 ML per minute) of the second shell component precursor solution (20 mL of 15 wt. % sodium silicate(aq)) using a suspended magnetic stirrer reactor at 300 RPM. The pH was kept constant at pH 7 by continuous injection of 1.6 M HCl(aq) and 1 M NaOH(aq) solutions. The capsules were then centrifuged every 10 minutes at 2500 RPM. The supernatant was discarded and the capsules were redispersed in deionized water.
[0217] To test whether the capsules would disintegrate, the slurry was diluted 10 times with deionized water. A drop of the resulting dilution was placed on a microscope microslide and allowed to dry overnight at room temperature. The next day, the dried capsules were observed under an optical microscope by light transmission to assess whether the capsules maintained their spherical shape (no cover slide was used). The capsules survived drying and did not disintegrate. The average volume weighted diameter of the capsules measured was 5.3 Mm and the CoV was 46.2%. The organic content in the shell was 0%.
[0218] Dimensions and values disclosed herein should not be understood as being strictly limited to the exact numerical values recited. Instead, unless otherwise indicated, each such dimension is intended to mean both the recited value and a functionally equivalent range surrounding that value. For example, a dimension disclosed as "40 mm" is intended to mean "about 40 mm."
[0219] All documents cited herein, including any cross-referenced or related patents or patent applications, and any patent applications or patents to which this application claims priority or the benefit thereof, are incorporated herein by reference in their entirety, unless expressly stated to the contrary, to the exclusion or otherwise limiting. The citation of any document shall not be deemed to be prior art to any invention disclosed or claimed herein, or to teach, suggest or disclose such invention, either alone or in combination with any other reference or references. Furthermore, to the extent that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this document shall apply.
[0220] While particular embodiments of the present invention have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the invention. It is therefore intended to cover in the appended claims all such changes and modifications that are within the scope of this invention.
Claims
1. A composition comprising a plurality of particles (90), the particles comprising: about 25% to about 99% by weight of a water-soluble carrier; a plurality of capsules (8) dispersed in the water-soluble carrier, the capsules comprising a core (4) and a shell (10) surrounding the core, the core comprising a perfume raw material; A composition wherein the shell comprises about 90% to 100%, optionally about 95% to 100%, optionally about 99% to 100%, by weight of the shell, of inorganic material.
2. The inorganic material is selected from metal oxides, semi-metal oxides, metals, minerals, and mixtures thereof, and optionally SiO 2 , TiO 2 , Al 2 O 3 , ZrO 2 , ZnO 2 , CaCO 3 , Ca 2 SiO 4 , Fe 2 O 3 , Fe 3 O 4 , clay, gold, silver, iron, nickel, copper, and mixtures thereof, optionally with SiO 2 , TiO 2 , Al 2 O 3 , CaCO 3 and mixtures thereof, optionally selected from SiO 2 2. The composition of claim 1 ,
3. a first shell component (6) in which the shell comprises a condensation layer and a nanoparticle layer, the condensation layer comprising a condensation product of precursors and the nanoparticle layer comprising inorganic nanoparticles (3), the condensation layer being disposed between the core and the nanoparticle layer; A second shell component (7) surrounding the first shell component, the second shell component (7) surrounding the nanoparticle layer.
4. The capsule comprises: an average volume weighted capsule diameter of from 10 mm to 200 mm, optionally from 10 mm to 190 mm; Average shell thickness between 170 nm and 1000 nm; characterized by one or more of a volumetric core to shell ratio of about 50:50 to 99:1, optionally 60:40 to 99:1, optionally 70:30 to 98:2, optionally 80:20 to 96:4; 4. The composition of any one of claims 1 to 3, wherein the first shell component comprises an organic content of 5 wt% or less, optionally 2 wt% or less, optionally 0 wt%, based on the weight of the first shell component.
5. The shell is a substantially inorganic first shell component comprising a condensation layer and a nanoparticle layer, the condensation layer comprises a condensation product of precursors; the nanoparticle layer comprises inorganic nanoparticles; the condensed layer comprising a substantially inorganic first shell component disposed between the core and the nanoparticle layer; an inorganic second shell component surrounding the first shell component, the second shell component comprises an inorganic second shell component surrounding the nanoparticle layer; The precursor comprises at least one compound selected from formula (I), formula (II), and mixtures thereof; Formula (I) is (M v O z Y n ) w and Formula (II) is (M v O z Y n R 1 p ) w and For formula (I), formula (II), or mixtures thereof, each M is independently selected from silicon, titanium, and aluminum; v is the valence of M and is 3 or 4; z is 0.5 to 1.6; and each Y is independently -OH, -OR 2 ,halogen, 【Chemistry 1】 -NH 2 , -NHR 2 , -N(R 2 ) 2 , and 【Chemistry 2】 is selected from R 2 is C 1 ~C 20 Alkyl, C 1 ~C 20 Alkylene, C 6 ~C 22 aryl, or 5- to 12-membered heteroaryl; the heteroaryl contains 1 to 3 ring heteroatoms selected from O, N, and S; R 3 is H, C 1 ~C 20 Alkyl, C 1 ~C 20 Alkylene, C 6 ~C 22 aryl, or 5- to 12-membered heteroaryl; the heteroaryl contains 1 to 3 ring heteroatoms selected from O, N, and S; and w is 2 to 2000; For formula (I), n is 0.7 to (v-1), and For formula (II), n is 0 to (v-1); Each R 1 is independently 1 ~C 30 Alkyl, C 1 ~C 30 Alkylene, C 1 ~C 30 Alkyl, halogen, -OCF 3 , -NO 2 , -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO 2 H, CO 2 C substituted with one or more of alkyl, aryl, and heteroaryl; 1 ~C 30 Alkyl, and C 1 ~C 30 Alkylene, halogen, -OCF 3 , -NO 2 , -CN, -NC, -OH, -OCN, -NCO, alkoxy, epoxy, amino, mercapto, acryloyl, CO 2 H, CO 2 C substituted with one or more of alkyl, aryl, and heteroaryl; 1 ~C 30 alkylene; p is a positive number of the maximum pmax, and pmax = 60 / [9 * Mw(R 1 ) + 8], Mw (R 1 ) is R 1 The composition according to any one of claims 1 to 4, wherein the molecular weight of the group is
6. The composition of claim 5 , wherein the precursor comprises at least one compound according to formula (I).
7. 7. The composition of claim 5 or 6, wherein the precursor comprises at least one compound according to formula (II).
8. The plurality of capsules are Average volume weighted capsule diameter of about 10 mm to about 200 mm; an average shell thickness of about 170 nm to about 1000 nm; a volume core to shell ratio of about 50:50 to 99:1; The composition of any one of claims 1 to 7, wherein the first shell component comprises an organic content of about 5% or less by weight, based on the weight of the first shell component.
9. wherein the compound of formula (I), formula (II), or both, is A polystyrene equivalent weight average molecular weight (Mw) of about 700 Da to about 30,000 Da; a degree of branching of 0.2 to about 0.6, and The composition of any one of claims 5 to 9, characterized by one or more of the following: a molecular weight polydispersity index of from about 1 to about 20.
10. The composition of any one of claims 5 to 10, wherein M is silicon.
11. 12. The composition of any one of claims 5 to 11, wherein for formula (I), formula (II), or both formula (I) and formula (II), Y is OR, and R is selected from a methyl group, an ethyl group, a propyl group, and a butyl group, and is optionally an ethyl group.
12. The composition of any one of claims 5 to 12, wherein the second shell component comprises a material selected from calcium carbonate, silica, and combinations thereof.
13. the inorganic nanoparticles of the first shell component comprise at least one of metal nanoparticles, mineral nanoparticles, metal oxide nanoparticles, or semi-metal oxide nanoparticles; Optionally, the inorganic nanoparticles are SiO 2 , TiO 2 , Al 2 O 3 , Fe 2 O 3 , Fe 3 O 4 , CaCO 3 , clay, silver, gold, or copper; Optionally, the inorganic nanoparticles are SiO 2 , CaCO 3 , Al 2 O 3 The composition of any one of claims 5 to 13, comprising one or more materials selected from:
14. The inorganic second shell component is SiO 2 , TiO 2 , Al 2 O 3 , CaCO 3 , Ca 2 SiO 4 , Fe 2 O 3 , Fe 3 O 4 , iron, silver, nickel, gold, copper, or clay, and optionally SiO 2 or CaCO 3 At least one of the following may be used: 2 The composition according to any one of claims 5 to 14, comprising:
15. 1. A process for treating laundry, comprising: providing laundry items to a washing machine; dispensing the plurality of particles according to any one of claims 1 to 14 into the washing machine; contacting the laundry article with the plurality of particles during a wash sub-cycle of the washing machine.
Citation Information
Patent Citations
Detergent composition
JP2010215806A
Deposition of lipophilic active materials in compositions containing surfactants
JP2011517323A
Delivery Particles
JP2011518654A
Microcapsules containing an active ingredient and a metal oxide shell, a method for producing the same, and their use
JP2011529392A
Capsules containing the active ingredient
JP2013531614A
